Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 905131922 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "Year 2004-2020", "HasGeospatialIssue is false" ] } The dataset includes 905131922 records from 12745 constituent datasets: 1 records from First report on Paratischeria from Asia (Lepidoptera: Tischeriidae). 1285 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 8346 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 23 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 247 records from MEXU/Leguminosae. 2190 records from DBRC Arvicola amphibius records 1925 - 2016. 1 records from Rediscovery of Lestes nigriceps Fraser, 1924 (Odonata: Lestidae) in eastern Cambodia. 5 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 26 records from Schulteich Heinrich-Mann-Schule. 2 records from Revision of the Central American and Mexican species of the Curtonotum murinum species complex (Diptera: Curtonotidae). 439 records from Implementación de la bioindicación en el Río Magdalena. 1 records from Redescription of the monotypic genus Cubacanthozomus (Schizomida: Hubbardiidae) and conservation status of its type-species. 1128 records from marine sediment metagenome Metagenome. 3769 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 371 records from Bannwald Burghauser Forst. 18164 records from R. L. McGregor Herbarium Vascular Plants Collection. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 13848 records from SEWBReC Bees, Wasps and Ants (South East Wales). 4 records from Marmacuma samimei gen. et sp. nov., (Peracarida; Cumacea; Nannastacidae) from Tarantian (Upper Pleistocene) sediments from the Sea of Marmara, Turkey. 10 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 2 records from Cryptochrysa Freitas & Penny, a generic homonym, replaced by Titanochrysa Sosa & Freitas (Neuroptera: Chrysopidae). 453 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 1 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 17 records from Colección de Referencia de Poríferos del Museo de Ciencias de la Universidad El Bosque. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 1 records from Description of Cephalotes specularis n. sp. (Formicidae: Myrmicinae) - the mirror turtle ant. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 14 records from Notes on the Stenus indubius group with descriptions of four new species from China (Coleoptera, Staphylinidae). 3153 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 90 records from Invasive species - Ruddy duck (Oxyura jamaicensis) in Flanders, Belgium. 11 records from National Botanic Garden Belgium - Myxomycetes. 5 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 2 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 11 records from Ektomykorrhizen auf VIP Alb (Wald). 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 2134 records from IAN herbarium - Embrapa Amazônia Oriental - Herbário Virtual REFLORA. 14012 records from INNS Data: All Taxa (West Wales). 8 records from Colección de hongos del Herbario "Jaime Andrés Rodríguez". LEB-Fungi. 46416 records from The Taiwan Roadkill Observation Network Data Set.. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 208 records from Condamine Alliance. 223 records from Données naturalistes de Ingénieurs écologues GEREA. 1 records from A new diploid species belonging to the Odontophrynus americanus species group (Anura: Odontophrynidae) from the Espinhaço range, Brazil. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 9886 records from sediment metagenome Metagenome. 4 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 185 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 2 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 2 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 460 records from Données naturalistes de Marie-France LECCIA. 170 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 12598 records from Microbial community in marine sediments. 60 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 8 records from Austrolebias ephemerus (Cyprinodontiformes: Rivulidae), a new annual fish from the upper Rio Paraguai basin, Brazilian Chaco. 1 records from Description of Sweltsa tibetensis sp. n. (Plecoptera: Chloroperlidae) from Tibet Autonomous Region of China. 45 records from données espèces - Expertise IPE 63. 37 records from Chronicle of Nature - Phenology of Mushrooms of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 1590 records from Herbier Louis-Marie (QFA) - Collection de lichens. 5 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 1709 records from suspended particulate matter Raw sequence reads. 55 records from USGS Alaska Science Center Polar Bear Maternal Dens. 1 records from Dolichopus nimbatus Parent, 1927 revisited, with two new synonyms (Diptera: Dolichopodidae). 434 records from Actualización de la base de datos del estado de Morelos de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 46 records from The Philippine hair wax spiders and their relatives: revision of the Pholcus bicornutus species group (Araneae, Pholcidae). 4 records from Taxonomic review and distribution of the genus Vespula Thomson, 1869 (Hymenoptera: Vespidae: Vespinae) from Vietnam. 3 records from Bees of the Hemihalictus series of Lasioglossum Curtis (Hymenoptera, Halictidae) in South Korea. 79090 records from Inventaire de la flore de Dordogne 2017. 494 records from Données naturalistes de la Société pour le Muséum d'Orléans et les Sciences (SOMOS). 5 records from Données du/de la naturaliste Kohn Annie provenant de la base de donnée du SINP Île-de-France CETTIA. 1997 records from Aves de la cuenca media del río Bogotá. 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 2 records from Updated information on genus Gomphidictinus (Odonata: Gomphidae) in China with description of Gomphidictinus tongi sp. nov.. 2107030 records from Observations du Conservatoire botanique national du Bassin parisien.. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 24 records from Steinbruch Mainz-Weisenau, 4.Jahr. 165 records from Echinodermata specimens of Kuroshio Biological Research Foundation. 310 records from Avifauna asociada a los manglares de Tribugá - Nuquí, 2016. 195581 records from Tasmanian Natural Values Atlas. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 58 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 51431 records from Macaulay Library Audio and Video Collection. 614 records from Inventario de la biota terrestre (florístico) y marina (invertebrados, peces y macroalgas bentónicos) del parque nacional Isla Isabel. 53 records from Museu Darder de Banyoles. 2 records from Two new species of Acontias (Acontinae, Scincidae) from the Mpumalanga Highveld escarpment of South Africa. 20 records from DMNS Egg Collection (Arctos). 70 records from Lepidopterous specimens of Yamagata Prefectural Museum. 47140 records from Vascular Plants, Field notes, Oslo (O). 6 records from Dactylobasis gen. nov. from Colombia, a new genus of Zygoptera with Teinobasini affinities (Odonata: Coenagrionidae). 56 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 1 records from The larva and pupa of Potamyia flavata (Banks 1934) (Trichoptera: Hydropsychidae): Description, life cycle, and notes on its biology. 41 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 1 records from Contribution to the genus Okinawepipona Yamane (Hymenoptera: Vespidae: Eumeninae) from Vietnam, with description of a new species. 1 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 42 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 8 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 287870 records from Florida Keys Reef Visual Census 2014. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 100 records from An updated checklist of aquatic plants of Myanmar and Thailand. 46316 records from Future climate change affects the microbiome and condition of habitat-forming kelp. 1564 records from Données naturalistes d'Océane ROQUINARC'H. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 55 records from Caracterización faunística de la Reserva Forestal Protectora Regional Brisas del Rincón. 20505 records from Herbarium Universitatis Daugavpiliensis. 5 records from Hyleina kaphetea, a new genus and species of clearwing moths from tropical Africa (Lepidoptera: Sesiidae: Sesiini). 2208 records from marine sediment metagenome Raw sequence reads. 3909443 records from International Barcode of Life project (iBOL). 1 records from Loneura Navás (Psocodea: Psocomorpha: Ptiloneuridae): new species from Brazil, and description of the female of Loneura maracaensis Garcia Aldrete, with a checklist of all known species of the genus. 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 601 records from LBV 100 - Artenvielfalt am Rothsee. 105 records from Données naturalistes de Xavier BONNET. 6787 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 971 records from azorean_vascular plants. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 1860 records from Plecoptera. 3 records from MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata - E. przewalskii species complex (Squamata, Lacertidae). 44 records from Flora und Fauna in unserer Kita. 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 2 records from A new species of and a new transfer from the millipede genus Polydrepanum Carl, 1932 (Polydesmida, Paradoxosomatidae, Polydrepanini). 5 records from New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae). 20745 records from Mesures compensatoires A65 (CDC Biodivsersité). 84 records from BIRDRACE Avinauten. 84 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 7 records from Re-description of Coeliccia erici Laidlaw, and the description of Coeliccia sameerae sp. nov. from Peninsular Malaysia (Odonata: Zygoptera: Platycnemididae). 3 records from Argiope hoiseni, a new species of the spider genus Argiope (Araneae, Araneidae) from Peninsular Malaysia based on morphology and molecular analyses. 650 records from Données 2016 de la Ligue de Protection des Oiseaux de Touraine. 10 records from NZCS Brownsberg Nature Park Monitoring. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 533 records from Collection Mollusca SMF. 5101 records from Lichen field notes, Oslo (O). 46282 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 35 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 7899 records from Données naturalistes de Benoit MARTHA. 14 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 114 records from Especies de peces registradas en el canal principal y afluentes de los ríos Lengupá y Upía en Boyacá. 105328 records from Observations occasionnelles Parc national des Pyrénées. 120 records from BIRDRACE The early birds. 1275 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 494 records from RECORD Orthoptera Data. 92 records from Protozoa Abundance_Microbial Parameters. 7 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 2 records from hips of Epidrepanus within the subtribe Drepanocerina (Coleoptera: Scarabaeidae: Scarabaeinae: Oniticellini), with the description of two new species. 51 records from Records of the Victorian Conservation Seedbank. 14294 records from Bird survey of Budai salt pans in Taiwan. 12 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 493 records from The digitization of plant specimens of NTU. 1722 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 1 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 1224 records from Upper Silesian Museum, Bird Observations. 423 records from DREAL Auvergne - Amphibiens - 2015. 554 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 1095 records from Données naturalistes de Quentin ROME. 3935 records from Lakes ediments of the Amazon River system Raw sequence reads. 6 records from Sächsische Schweiz (Pfaffenstein). 11944 records from Données ONEMA BDMAP 2014. 562 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 10 records from Chronicle of Nature - Phenology of Arachnids of FSBI Zeya State Nature Reserve. 4298 records from ColRest_Raw1. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 4610 records from Wetland Algae. 1157 records from SNH Bat Casework records 1970-2007. 5 records from Description of the first Caribbean Oscarellidae (Porifera: Homoscleromorpha). 2354 records from Recopilación de Información de FLORA en la Jurisdicción de CORNARE, hasta el año 2015. 4335 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 606 records from Chronicle of Nature - Phenology of Plants of Kaniv Nature Reserve. 7 records from Review of the genus Amemboides Polhemus & Andersen, 1984 (Hemiptera: Heteroptera: Gerridae) from China, with description of a new species. 179 records from Données du/de la naturaliste Barande Serge provenant de la base de donnée du SINP Île-de-France CETTIA. 496 records from Naturhistorisches Museum Mainz, Botanical Collection. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 1087 records from Tree species composition of natural forest islands in a savanna matrix in the northern Brazilian Amazonia. 84 records from Roter Berg Werdau (Leubnitz). 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 3674 records from Données naturalistes de Charlotte PICARD. 2 records from The genus Sinodiaptera Dellacasa (Coleoptera: Scarabaeidae: Aphodiinae) in Taiwan. 2 records from First record of the genus Eriopisella Chevreux, 1920 (Crustacea, Amphipoda, Senticaudata, Eriopisidae) from Australia, with the description of a new species, Eriopisella moretoni sp. nov.. 14423 records from University of California Santa Barbara Invertebrate Zoology Collection. 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 634 records from Colección de Laurales, Liliales, Lycopodiales, Magnoliales y Malpighiales del Museo Botánico CORD - IMBIV. 14 records from Two new species of Nullana from southern Brazil (Hemiptera: Cicadellidae: Gyponini) with key to males. 26 records from IRAD Cameroon insect collection. 76 records from Données du/de la naturaliste D'HINZELIN MARCEL provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from The Shiny Cowbird, Molothrus bonariensis (Gmelin, 1789) (Aves: Icteridae), at 2,800 m asl in Quito, Ecuador. 235 records from The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species. 8008 records from Données chiroptères récoltées pour l'étude des GPSO. 627 records from Etude des coléoptères de l'ENS de Voulangis (77). 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 7098 records from Grand_Site_Sainte-Victoire_2017_12_18. 8 records from On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea. 13 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 57 records from CSIRO Yellow Box Fragmentation Project. 3363 records from Entomology Collection at the Natural History Museum of Utah. 11 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 1099 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 111 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (1), 2009 - Données faune. 43071 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 8 records from Xenosinelobus balanocolus, a new tanaidid genus and species (Crustacea: Peracarida: Tanaidacea) from barnacles on intertidal rocky shores and seawalls in the Singapore Strait. 3633 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 50598 records from Fish specimens of Kagoshima University Museum. 2 records from A revision of Colletes Latreille (Hymenoptera: Colletidae: Colletinae) from Brazil, Paraguay and Uruguay. 27 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 14 records from UTEP Invertebrates (Arctos). 6 records from Notes on the first instar larvae of the genus Tipula (Diptera: Tipulidae). 59 records from Schulteich Freie Waldorfschule Darmstadt. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 4 records from A new skink of the genus Scincella Mittleman, 1950 (Squamata: Scincidae) from Ba Den Mountain, Tay Ninh Province, southern Vietnam. 1391 records from RIVM (NL) - Earthworm Observations in Soil Samples. 8 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 7648 records from AMNH Bird Collection. 111 records from Foto trampeo al interior de las áreas del Banco de Hábitat del Meta de Terrasos. 2756 records from Données du/de la naturaliste Chevallier Laurent provenant de la base de donnée du SINP Île-de-France CETTIA. 1949 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 4 records from Evidence for the continued presence in New Zealand of Homotrysis macleayi (Borchmann, 1909) (Coleoptera: Tenebrionidae: Alleculinae). 577 records from Ensemble des données Odonates. 2134 records from Kurzflügler_Raw1. 170 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 873 records from DOW-2. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 2 records from Re-description of Orchestia stephenseni Cecchini, 1928: designation of neotype and senior synonym to Orchestia constricta A. Costa, 1853 (Crustacea: Amphipoda: Talitridae) by Reversal of Precedence. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2049 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 2362 records from RECORD Bryopsida Data. 1407 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 12 records from Art´n Vielfalt im Kinderwald. 13 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 2100 records from Amphibian and reptile data for Dumfries and Galloway.. 770 records from Chronicle of Nature - Phenology of Birds of Pinezhsky State Nature Reserve. 514 records from Museu de Ciències Naturals de Barcelona: BGJBB. 1 records from A new record and two new species of Cryptochironomus Kieffer, 1918 from China (Diptera, Chironomidae). 21 records from The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 10600 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 13376 records from OPIE_National_2017_12_18. 520 records from UWIZM Molluscs. 2990 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Trawl. 23263 records from CAS Herpetology (HERP). 65 records from Oxic sediment - Extracellular Metagenome. 3163 records from MCP-Aves - Coleção de Aves. 74 records from Área Selva de Florencia- Cantidad de área ocupada selva_2018. 2 records from Three new species of Psyrassa Pascoe, 1866 (Coleoptera, Cerambycidae, Cerambycinae). 2 records from Danio htamanthinus (Teleostei: Cyprinidae), a new species of miniature cyprinid fish from the Chindwin River in Myanmar. 3244 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 76704 records from EDP Foz Tua: Terrestrial Birds, Spring (point counts) - Ecological Monitoring Program [2011-2017]. 22 records from orthopteracollections-nhmj-ioj. 8 records from Bird specimens of Saitama Museum of Natural History. 178 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 19 records from Genus Bungona Harker, 1957 (Ephemeroptera: Baetidae) from China, with descriptions of three new species and a key to Oriental species. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 306 records from Diagnostic des Espaces Naturels Sensibles des Yvelines. 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) and the first record of C. otai from Son La Province, Vietnam. 788 records from Waldränder der Frankenhöhe (Rothenburg ob der Tauber). 6 records from Two new species of the conger eel genus Bathycongrus (Anguilliformes: Congridae) from Taiwan. 3 records from Collections of Bioklass, school #179, Moscow. 523475702 records from EOD - eBird Observation Dataset. 577 records from Données du/de la naturaliste Houpert Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 54 records from Mycology collection, Norwegian Forest and Landscape Institute. 11 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 2 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 6 records from The megisthanid mites (Mesostigmata: Megisthanidae) of Australia. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 3321 records from Colección de Solanales del Museo Botánico CORD - IMBIV. 32 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 5 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 404 records from Actualización de las bases de datos de las colecciones de plantas vasculares y macromicetos del herbario de la UJAT. 2 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 8531 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 29 records from UWIZM Anoles. 106 records from West African pholcid spiders: an overview, with descriptions of five new species (Araneae, Pholcidae). 1 records from A new species of Dicrotendipes (Diptera: Chironomidae) from Florida. 2 records from The genus Cylloepus Erichson, 1847 (Coleoptera: Elmidae: Elminae) new species and combinations. 2 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 1069 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 1212 records from Phase 2 Lowland Grassland Survey of Wales. 409 records from Invasive Non-Native Species, Outer Hebrides. 2 records from Revision of the species related to Lalagetes subfasciatus Boheman and transfer of remaining Lalagetes species to other genera of Embrithini (Coleoptera: Curculionidae: Entiminae). 2 records from Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini). 1110 records from FFH-Gebiet "Calwer Heckengäu". 4 records from Naturalis Biodiversity Center (NL) - Crustacea. 813 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE233. 1 records from Ecological Guild Evolution and the Discovery of the World’s Smallest Vertebrate. 576 records from DSW-2. 45604 records from Bob Merritt Coleoptera Dataset. 101 records from Component analysis of TV-guided grab sampler GeoB10071-5. 2 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 258 records from Computarización de la Colección de Referencia de Nemátodos Fitopatógenos del Centro Nacional de Referencia Fitosanitaria de la Dirección General de Sanidad Vegetal. 14736 records from Mise en place d'un suivi scientifique des rhopalocères pour la production d’indicateurs de biodiversité. 418 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 774427 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 26 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 144017 records from DATAVES. 150 records from Mamíferos no voladores de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 103 records from Projet Diable de mer - AILERONS. 296 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 23 records from Herpetofauna asociada a la cuenca del río Quito - Chocó, 2014. 4 records from Two new species of the genus Narcotica Sugi, 1982 (Lepidoptera: Noctuidae: Acronictinae). 28 records from Caracterización de la fauna del páramo del Duende, litoral del San Juan, Chocó. 477 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 1 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera Oecophoridae) V. The unistriatella species group, with descriptions of seven new species. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 209 records from The Broward College Insect Collection. 14 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 1 records from A contribution to the knowledge of the subfamily Panagaeinae Hope, 1838 from Africa. Part 3. Revision of the Craspedophorus strachani and C. brevicollis groups (Coleoptera: Carabidae). 103 records from Schwanseepark (87645 Schwangau). 9653 records from Ecosphère_2017_12_18. 4520 records from Données d'observation de la mégafaune marine issues des campagnes océanographiques en France métropolitaine. 324 records from Chronicle of Nature - Phenology of Plants of Bryansk Forest Nature Reserve. 8 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 114 records from BIRDRACE VIE will rock you!. 549 records from Isle of Wight non-native invasive species. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 581 records from Floristic records in the Moscow and Novgorod regions. 10349 records from Macrophyte Lake Data. 308 records from Weber State University Herbarium. 10520 records from Données LPO Réserve naturelle régionale du marais de la Vacherie. 19 records from The Onthophagus fuscus (Coleoptera: Scarabaeidae) species complex: an update and the description of a new species. 3176 records from SIM-Fungal records compiled by Joan Montón. 1348 records from Plant specimens of Obihiro Centennial City Museum. 97959 records from Western Australian Museum provider for OZCAM. 1 records from Two new Mesenchytraeus species (Annelida: Clitellata: Enchytraeidae) from Changbai Mountain, China. 157 records from Carabidae of the Carpathians. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 2 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 915276 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 2 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 1 records from Canadian Lakes Loon Survey. 6921 records from Xylophaga in situ Eclusion Experiment. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 735 records from Protistan plankton diversity along salt gradient. 33 records from Waldstück am Schullandheim Bad Bederkesa. 4632 records from Inventaire de la flore du Grand Poitiers 2009. 110 records from Polish gene bank – passport data of plants accessions which are important in human life. 10 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 3150 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 707 records from SMDB - Santa Maria Departamento de Biologia. 1 records from Données naturalistes d'Olivier DELZONS. 68 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 720 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 32 records from Caracterización Floristica del Paramo de Frontino o del Sol. 1831 records from Modelaje de la Distribución geográfica de Pinus pseudostrobus y P. leiophylla. 75 records from Données du naturaliste Matthieu Gouirand. 85 records from Birdrace-Die_Paradiesvögel-Herford. 174 records from BIRDRACE Bon(n)apartemöwen. 6 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 11 records from New species of the genus Aztecatopse Haenni & Huerta from Mexico (Diptera, Scatopsidae). 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 3 records from Plathelminthes - SMF. 1545 records from NatureMap Calcrete Survey. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2201 records from Insect specimens of Rikuzen-Takata City Museum. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 10 records from Cowan Tetrapod Collection - Mammals. 228 records from Actualización de la información sobre los maíces criollos de Oaxaca. 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 88 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 2 records from A new species of Rock Gecko genus Cnemaspis (Squamata: Gekkonidae) from Western Sarawak, Malaysia. 23 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 6 records from The lestevoides species group of the genus Geodromicus Redtenbacher, 1857 (Insecta: Coleoptera: Staphylinidae: Omaliinae). 4 records from The genus Sicoderus Vanin 1986 (Coleoptera: Curculionidae: Curculioninae: Erodiscini) in the West Indies. 1737 records from Données Nature 18 - Études faune 2016. 5109 records from University of Minnesota Insect Collection. 16 records from Insect Collections of Okomu National Park- Nigeria. 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 412 records from Heinersdorfer Sumpfwiese. 35728 records from ARABEL - Arachnologia Belgica. 8 records from The genus Asiagomphus in Vietnam, with descriptions of three new species, and first descriptions of the male of Asiagomphus auricolor (Fraser, 1926) and of the female of Asiagomphus reinhardti Kosterin & Yokoi, 2016 (Odonata: Gomphidae). 3168 records from Arctic Species Trend Index (ASTI) : Marine. 184 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 5184 records from Fungi on beech (Fagus sylvatica) wood, Halland, Sweden. 8473 records from Wolli Creek Preservation Society Bird Survey. 4283 records from LSUMZ (LSU MNS) Fishes Collection. 297 records from MLZ Bird Collection (Arctos). 63 records from Inventaire des espèces végétales de la vallée de Gounti Yéna (Niamey). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 6 records from 2. Donauinsel bei Entau. 10 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 8 records from Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species. 5 records from DREAL_PACA_-_N2000_-_Office_National_des_Forêts_04_2017_12_18. 4 records from Coeliccia lecongcoi sp. nov., a new damselfly from the Central Highlands of Vietnam (Odonata: Zygoptera: Platycnemididae). 2 records from A new species of Trachylepis (Squamata: Scincidae) from Central Africa and a key to the Trachylepis of West and Central Africa. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 148143 records from ImageDOP Bentic Video Annotations in the Faial-Pico Channel in 2011. 12817 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 62 records from SEWBReC Springtails and allies (South East Wales). 559715 records from Collation of spatial seagrass data from 1984 - 2014 for the Great Barrier Reef World Heritage Area (GBRWHA) (NESP TWQ 3.1, TropWATER, JCU), Australia (1984-2014). 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 749 records from Carabidae of Wales and England. 2 records from Orientatractis brycini sp. nov. (Nematoda: Atractidae) from characiform freshwater fishes in Gabon, Africa. 1220 records from The Himalayan Uplands Plant database (HUP Version 1). 5 records from Three new minute leaf litter beetles discovered by citizen scientists in Maliau Basin, Malaysian Borneo (Coleoptera: Leiodidae, Chrysomelidae). 131 records from Artenvielfalt auf dem Schulgelände. 110 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 5 records from Two new littoral species of the genus Anurida Laboulbène, 1865 (Collembola, Neanuridae) from the Pacific coast of Asia. 18868 records from North Sea plastic incubation and reference communities, raw sequence reads. 120 records from Royal BC Museum - Herpetology Collection. 3 records from Two new and one newly recorded species of Polypedilum Kieffer 1912 with DNA barcodes from Oriental China (Chironomidae: Diptera). 1507 records from National Museum of Natural Science. 165 records from Diversidad de anfibios en tres coberturas vegetales y su relación con actividades antrópicas (amenazas) presentes en el Parque Nacional Natural Tatamá y su área de influencia.. 238 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 215 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 69 records from Global Ocean Sampling Expedition. 69 records from BIRDRACE Pfeifenten. 10 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 39 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 190 records from Données de la structure ONEMA/AFB provenant de la base de donnée du SINP Île-de-France CETTIA. 146 records from Données de la naturaliste Laurence Beauchamp. 1 records from Collections ichtyologiques et herpétologiques (BOUM). 2 records from A new species of the genus Takydromus (Squamata, Lacertidae) from southwestern Guangdong, China. 2831 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 1 records from Ta xonomic study on the Chinese Steninae (Coleoptera, Staphylinidae), with descriptions of three new species of the Genus Stenus Latreille. 54 records from Données "faune" de LABBAYE Olivier pour le SINP île de France. 14 records from Données naturalistes de ROLLAND Blandine. 9 records from Taxonomic revision of Brazilian genus Tyrannoseira Bellini & Zeppelini, 2011 (Collembola, Entomobryidae, Seirinae). 11 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 5 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 222 records from Lichens of North-Eastern Poland. 83 records from Données du/de la naturaliste Swoszowski Florie provenant de la base de donnée du SINP Île-de-France CETTIA. 1983 records from NE Scotland fish records 1800-2010. 39 records from Taxonomy and Biogeography without frontiers – WhatsApp, Facebook and smartphone digital photography let citizen scientists in more remote localities step out of the dark. 6 records from Cochlostoma revised: the subgenus Lovcenia Zallot et al., 2015 (Caenogastropoda, Cochlostomatidae). 609 records from Arácnidos - Miriápodos de la expedición al Río Apaporis - Proyecto Colombia BIO. 15 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 4 records from Moriphila furva gen. and sp. nov. (Hemiptera: Psylloidea: Homotomidae), a new jumping plant-louse from Korea associated with Morus australis (Moraceae). 5 records from UWYMV Herpetology Collection (Arctos). 46 records from Liether Park (LMS), 5a. 11873 records from Midden-Limburg Fish Ponds Survey. 155 records from Herbarium (ICEL). 26178 records from Herbarium Senckenbergianum (FR) - Fungi. 5 records from New species, redescriptions and a new combination of Acanthocyrtus Handschin, 1925 and Amazhomidia Cipola & Bellini, 2016 (Collembola, Entomobryidae, Entomobryinae). 81 records from Mamíferos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 2 records from A new species of the ant genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae) from the Caribbean region. 2 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 15876 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 5 records from Cactophilic Drosophila and Opuntia. 1469 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 238 records from Vegetación asociada a la ciénaga de Bete, municipio del Medio Atrato, Chocó 2008. 2 records from Limnebius (Limnebius) agnieszkae sp. n. from the Crimean Peninsula (Coleoptera: Hydraenidae). 3426 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 20712 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 3260 records from Leicestershire and Rutland Aculeate Records. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 16539 records from Suivi Temporel des Libellules (STELI). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 14057 records from WCPS Bird Survey Project. 51 records from Anfibios y reptiles de la expedición en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 746 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 106 records from Sylter Meerstrandläufer. 3 records from Taxonomic review of the genus Dascillus Latreille, 1797 in the Western Palaearctic (Coleoptera: Dascillidae). 661 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 2 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 24959 records from Fungal occurrences from the Basque Country and neighbouring areas: ARAN-Fungi. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 66 records from Ensemble des données Orthoptères. 672 records from University of Ghana - Ghana Herbarium. 1 records from Pseudaeginella telukrimau sp. n., a new species of caprellid (Crustacea: Amphipoda) from Malaysia. 10381 records from Inventaire de la flore de Charente-Maritime 2018. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 2 records from A new species of Pelthydrus (s. str.) Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae: Laccobiini). 225 records from Tillegg Røtinga i Os. 10 records from Données naturalistes de Franck MERLIER. 1343 records from BSM marine Targeted Locus. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 2808 records from Natura 2000 Vallée de la Seille. 8654 records from Survey data of tidal flats on the Monitoring sites 1000 project, BDCJ. 2 records from The identity of Aplocheilus andamanicus (Köhler, 1906) (Teleostei: Cyprinodontiformes), an endemic Killifish from the Andaman Islands, with notes on Odontopsis armata van Hasselt. 6 records from Données naturalistes de THÉVENOT Jessica. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 35061 records from Inventaire de la flore de Lot-et-Garonne 2017. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 117 records from Área Tatama - Densidad poblacional Bangsia Tatama, 2018. 23138 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 2507 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé t du Plateau. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 232 records from Monitoreo biológicos en la cuenca Frayle, ARA - RARE - CVC – Asociación Calidris. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 16 records from Birds Specimens of Akita Prefectural Museum. 1 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 103 records from Données du naturaliste JAPIOT Xavier provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 35601 records from TWIC Biodiversity Field Trip Data (1995-present). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 100 records from Données naturalistes de LE GLOANEC Vincent. 407 records from Megafaunal data from the 2009 BIOFUN trans-Mediterranean deep-sea cruise. 84 records from SNH Invertebrate Site Condition Monitoring 2015: Dunhog Moss SSSI. 136 records from Oberes Schindelbachtal. 14249 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 88 records from Seagrass_data_Solomon Islands_2018. 1 records from On the identity of the Palearctic species of the wolf spider genus Trebacosa (Araneae: Lycosidae). 323 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 67958 records from The 6-7th National Survey on the Natural Environment: Vegetation Survey. 2 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 134 records from Mycoblitz 2017 - IRBV et Cercle des Mycologues de Montréal. 1 records from A new crayfish of the genus Cambarus Erichson, 1846 (Decapoda: Cambaridae) from an under-sampled habitat type in central Ten- nessee, USA. 30340 records from River Biologists' Database (EPA). 49794 records from CABI Africa Invasive and Alien Species data. 2047 records from Eurobodalla Regional Botanic Gardens. 55 records from Great Eastern Ranges - Slopes to Summit. 13 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 75 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 13604 records from Tiroler Landesmuseum Ferdinandeum. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 464 records from Colección de Mamíferos del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-M). 1933 records from Análisis de Integridad Biológica en la Reserva Forestal Protectora Regional Bitaco. Convenio CVC- Univalle 108 de 2017. 491 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 109191 records from National Mammal Atlas Project, online recording. 9716 records from Epibenthos and demersal fish monitoring at long-term monitoring stations in the Belgian part of the North Sea. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 5938 records from Odonata records from RSPB Reserves 1970-2009. 1802 records from Diatomeas bentónicas de los oasis de Baja California Sur. 850 records from Données supplémentaires Atlas des Mammifères marins. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Quaid-i-Azam University Herbarium. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 7 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 18 records from Anfibios presentes en el Cerro Jánano. 119 records from Données espèces - Expertise IPE 79. 6 records from Two new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the Shevaroy massif, Tamil Nadu, India, with a preliminary ND 2 phylogeny of Indian Cnemaspis. 6710 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 941054 records from NBIS Records to December 2016. 115 records from Nezara viridula records held by the Royal Horticultural Society. 2 records from A new species of cascade frog (Amphibia: Ranidae) in the Amolops monticola group from China. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 654 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 61 records from South American Antarctic Marine Biodiversity Literature. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 2 records from Description of Lacon mertliki sp. nov. (Coleoptera: Elateridae: Agrypninae) from the Hyrcanian forest ecoregion, with a key to the Lacon species of Iran. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 477 records from Blue Mountains Swamp Archaea. 5 records from Description of two new species of Magnispina and a new hypothesis of phylogenetic relationships for Heteropachylinae (Opiliones: Laniatores: Gonyleptidae). 26 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 13 records from Species of Prioninae, Parandrinae, Lepturinae (Insecta, Coleoptera, Cerambycidae) and Disteniidae (Insecta, Coleoptera) from east Paraná State (Brazil), with three new geographic distribution records. 4930 records from SPC PROCFish/C Invertebrates Observations Papua New Guinea 2006. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 108 records from Specimen references on the Rubiaceae family held by theTAN Herbarium. 17 records from Thirteen new records of ferns from Brazil. 129 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 23 records from A new species of the genus Watsonidia Toulgoët, 1981 (Lepidoptera, Erebidae, Arctiini): example of polymorphism in the Amazon of Peru. 4 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 105 records from STERF 2014/2015 Hasparren (64) par l'association EcoGIS. 117904 records from Biological Impacts of Ocean Acidification. 78 records from Données de la naturaliste Anna Even. 3 records from Survey of sand flies (Diptera: Psychodidae: Phlebotominae) in Guajará-Mirim State Park forest reserve, near the Brazil-Bolivian border, with a description of Pintomyia fiocruzi, a new sand fly species. 2512 records from Données du Busard de Maillard (Circus maillardi) du Parc national de La Réunion. 11925 records from Données du naturaliste Julien Birard provenant de la base de donnée du SINP Île-de-France CETTIA. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 116 records from Streuobstwiese Stedar 2009. 57 records from pangolin and pangolin products seized by the customs and pangolin public aided record from 2010 to 2019. 1 records from A new species of Gymnophthalmus (Squamata: Gymnophthalmidae) from sand dunes of the Llanos of Apure, Venezuela. 81 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 14 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 1123 records from Sistematización de la colección de peces del centro de México. 8 records from Systematics, biogeography and host-plant relationships of the Neotropical jumping plant-louse genus Russelliana (Hemiptera: Psylloidea). 340 records from Ictiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 8 records from Die Bachspezies 2008/2009. 834 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 35 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Results of palynological analysis of Hole 302-M0004C. 3 records from Two new species and a key to the dustywings of Mexico (Neuroptera, Coniopterygidae). 135 records from Globigerinita spp. in sediment core MSM05/5_712-2. 42234 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 1 records from Further revision of the genus Bythotrephes Leydig (Crustacea: Cladocera: Onychopoda): redescription of B. brevimanus Lilljeborg, reevaluation of B. cederströmii Schödler, and description of a new species of the genus. 8 records from Streuobstwiese. 15 records from Description of lithologic section units of IODP Hole 325-M0041A. 21 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 13563 records from FKSE-Herbarium of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 3 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3280 records from NE Scotland other invertebrate records 1800-2010. 667 records from SEWBReC Fish (South East Wales). 1 records from Registro de Ateles belzebuth (mono araña) en el municipio de Yopal, departamento de Casanare. 494 records from Datos de ocurrencia de triatominos americanos del Laboratorio de Triatominos del CEPAVE (CONICET-UNLP). 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. GEPOG & LPO. 16702 records from RNF - Données du Conservatoire d'espaces naturel Franche-Comté. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 97 records from Données opportunistes odonates récoltées par le CPIE Seignanx et Adour entre 2011 et 2015. 3279 records from Estudio taxonómico distribucional de los peces del estado de Chiapas, México. 73534 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 8088 records from Données Entomologiques A. HORELLOU 1988-2018. 5 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 337 records from Antarctic and SubAntarctic Ophiuroidea - MNA (Section of Genoa). 1 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 632 records from 2019_NSMK_PL. 30 records from Geführte Wanderung im Eselsbachtal. 6858 records from Benthic foraminifera abundance in per cent of Hole PRAD1-2. 1 records from A new species of the genus Larutia (Squamata: Scincidae) from Gunung Penrissen Sarawak, Borneo. 22 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1624 records from Herbier National de Guinée (HNG). 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 37324 records from Inventaire de la flore des Landes 2017. 455 records from EDIT - ATBI in Gemer area (Slovakia). 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 19574 records from Global compendium of Aedes albopictus occurrence. 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 325 records from Inventaire malacologique de la RNR des Marais de Stors. 2672 records from données aranéologiques de LEDOUX Jean-Claude. 88 records from Teich Berlin Wuhlheide. 40 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 5 records from A new Epeorus (Caucasiron) (Ephemeroptera: Heptageniidae) species from Turkey based on molecular and morphological evidence. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 28 records from AKG-Gelände (Bensheim). 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 2 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 160 records from Données espèces - Expertise IPE 37. 3 records from A new species of velvet skate, Notoraja sereti n. sp. (Rajiformes: Arhynchobatidae) from Papua New Guinea. 80 records from Wairambar Rainforest Species list 2018. 67 records from Données du naturaliste JOB Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 343 records from Observations de cétacés à partir de navires de pêches: campagnes PETRACET/PROCET et OBSMAM - Observatoire PELAGIS. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 2 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1534 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 2 records from Moenkhausia restricta, a new species from the upper Rio Negro, Amazon basin, northwestern Brazil (Characiformes: Characidae). 417 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 19 records from Four new species of Paranaitis Southern, 1914 (Phyllodocidae, Annelida) from southern and southeastern Brazil. 1 records from Données naturalistes de Caroline DAGNEAU. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 1060 records from Banco de Germoplasma de Especies Nativas del Instituto de Ecologia y Ambiente Humano - UNSA- Arg. 2 records from A new species of Hemigrammus Gill 1858 (Characiformes: Characidae) from the upper Rio Negro, Amazon basin, Brazil. 123 records from City of Edinburgh Natural Heritage Service - Hillend Wildflower Meadow Survey. 4 records from Description of Brachymeria philornisae sp. n. (Hymenoptera: Chalcididae), a parasitoid of the bird parasite Philornis trinitensis (Diptera: Muscidae) in Tobago, with a review of the sibling species. 101 records from Naturgrundstück (Eutin). 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 139 records from données araneologiques de LEENKNEGT Virginie. 2 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 2 records from The myth of monophagy in Paralobesia (Lepidoptera: Tortricidae)? A new species feeding on Cypripedium reginae (Orchidaceae). 75 records from Checklist of rust fungi (Pucciniales) occurring in Portugal. 111 records from Données naturalistes de Mr MONTAGNER Sylvain. 3 records from Two new species of Parandrinae (Coleoptera: Cerambycidae) in the genera Parandra and Acutandra from South America. 1645 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 1000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 1 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 35421 records from Données de l'Observatoire de la Faune de Bourgogne. 17 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 1 records from Echinodera (Ruteria) soumasi sp. n. from Greece (Coleoptera, Curculionidae). 4 records from Osmiine bees of the genus Haetosmia (Megachilidae, Osmiini): biology, taxonomy and key to species. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 53 records from Descriptions of two new species of Brachyzapus Gauld & Dubois (Hymenoptera: Ichneumonidae: Pimplinae) from South Korea with key to a Palaearctic species. 2 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 101 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Echinodermata. 89 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 521 records from Données du partenariat Imerys - UMS PatriNat - 2018-2020. 1208 records from Microbial diversity studies of Arabian Sea sediment. 179 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 4142 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 132 records from Echinoderms from the Seaflower Biosphere Reserve. 24 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 368 records from Biological Recording in Scotland - Bumblebee Survey. 13867 records from Allan Herbarium (CHR). 82 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/562-1. 13183 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 1 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 593 records from Mamíferos voladores laguna El Tinije. 92 records from Birkenloh. 183 records from Mission ONF 2008 d'inventaire de la Réserve naturelle de la Trinité. 788 records from Species observations during citizen science expeditions. 23 records from MVZ Herp Observations (Arctos). 1 records from New records of benthic hydroids (Cnidaria: Hydrozoa) from the coast of Oaxaca, Mexico. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 2 records from Collection Cnidaria fossil SMF. 1 records from A new Portholefish of the genus Diplophos (Stomiiformes: Gonostomatidae) from the western Pacific Ocean. 459 records from NSG Karwendel. 246 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 5 records from A new Oreonetides Strand, 1901 from the Russian Far East (Araneae, Linyphiidae). 251 records from Données naturalistes d'Olivier LAURENT. 2 records from Revision of the Afrotropical genus Susua Lugo-Ortiz & McCafferty 1998 (Ephemeroptera: Baetidae: Protopatellata). 20831 records from Restauración y conservación de Isla Guadalupe. 1 records from Fiocruz/COLPROT - Coleção de Protozoários. 729524 records from SA Flora (BDBSA). 122 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 98 records from Warnowtal (Rostock). 2 records from A new genus of the mite family Scutacaridae (Acari: Heterostigmata) associated with Trinervitermes trinervoides (Isoptera: Termitidae) from South Africa. 25 records from Données naturalistes de DUNESME Caroline. 124 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 6 records from Wuhle - Brücke / B1. 2 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 1966 records from Marie-Victorin Herbarium (MT) - Bryophytes. 189 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 45331 records from National Benthic Inventory. 2541 records from Marine Non Native Species records from Natural Resources Wales (NRW) Monitoring Research and Ad-hoc Sightings. 4 records from On the taxonomy of the subgenera Cyabarda Karisch, 2013, Idiovulpecula Karisch, 2013 and Paravulpeculella Karisch, 2013 of the genus Cyana Walker, 1854, with descriptions of three new species from Africa (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 65 records from Pêches électriques de sauvetage de 2015 à 2017. 19066 records from IMPACT OF SAHARAN DUST DEPOSITION ON BACTERIOPLANKTON IN MARINE SURFACE WATER. 32 records from UAM Herbarium (ALA), Algae Collection (Arctos). 219 records from Etude naturaliste des landes et pelouses à Fulchiron, Maisse (91). 63085 records from Alien plant presence dataset from the point-radius plot surveys in 2010-2015 in Taiwan. 2089 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1798 records from 3Soil16S. 2584 records from Données de la structure ANCA (les Amis Naturalistes des Coteaux d'Avron) provenant de la base de donnée du SINP Île-de-France CETTIA. 560 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 13637 records from Jeu de données de la Société limousine d'Etude des Mollusques. 76 records from BIRDRACE Nachtigallen. 134 records from schulgarten. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 2 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 193 records from Small rodents trapped in old growth forest in Vegårshei, Norway. 111 records from BIRDRACE Die Wendehälse. 3 records from Review of genus Hydropsyche Pictet 1834 (Insecta: Trichoptera: Hydropsychidae) from India. 1 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 6 records from Fiocruz/CAVAISC - Coleção de Artrópodes Vetores Ápteros de Importância em Saúde das Comunidades. 2 records from Two new species of Aphelochaeta (Annelida: Polychaeta: Cirratulidae) from Korean waters. 3436 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 418 records from Utah State University, Intermountain Herbarium. 5541 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 104 records from Caracterización Florística de un Área Degradada por Actividad Minera en la Costa Caucana. 119 records from Baltic Sea Basin sediments diversity Raw sequence reads. 746 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 146 records from La Colección Herpetológica de la Estación de Biología Tropical Los Tuxtlas, Veracruz. 3333 records from Mammalogy Collection - Royal Ontario Museum. 2 records from Rivulus kayapo n. sp. (Teleostei: Cyprinodontiformes: Rivulidae): a new killifish from the serra dos Caiapós, upper rio Araguaia basin, Brazil.. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 16946 records from Seasearch Marine Surveys in the Isle of Man. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 13872 records from CAS Entomology (ENT). 8 records from Naturalis Biodiversity Center (NL) - Pisces. 166197 records from Carnet B Lorraine. 1 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 3711 records from Dipterists Forum: Field Week 2015 (Nottinghamshire). 61 records from PACA-Bryophytes - Herbarium Anchieta - Aloysio Sehnem. 139 records from Myxomycetes collection of the University of Eastern Finland. 2673 records from Données naturalistes d'Emmanuel SECHET. 2873 records from Enquête participative "Lichens forestiers d'Auvergne et du Massif Central". 317831 records from Seasearch Marine Surveys in England. 62101 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 33 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 2 records from Two new Opadometa species (Araneae: Tetragnathidae) from Sarawak, Malaysia. 79 records from BIRDRACE Blinde Hühner. 3 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 6 records from The discovery of Lepidocyrtoides Schött, 1917 (Collembola, Entomobryidae, Entomobryinae) from the New World, including three new species from Brazil and one from Australia. 1 records from Mites of the family Parasitidae Oudemans, 1901 (Acari: Mesostigmata) from Japan: a new species of Vulgarogamasus Tichomirov, 1969, and a key to Japanese species. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 5592 records from Riqueza de especies y biodiversidad edáfica de una zona de humedales del Parque Nacional Arrecife de Puerto Morelos, Quintana Roo, México. 58 records from Collection Trichoptera - SMF. 43318 records from Inventaire de la flore des Landes 2016. 11 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 1 records from Concentración Lixiviados. 113 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 1 records from A new species and a new record of genus Hexacentrus Serville, 1831 (Orthoptera: Tettigoniidae: Hexacentrinae) from India. 944 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 4 records from Two new remarkable genera and two new species of Gyponini (Hemiptera: Cicadellidae: Iassinae) from Brazil. 11 records from Espèces envahissantes de la Guinée forestière extraites dans la base de données de CRRA Sérédou Macenta, IRAG.. 1 records from Description of two new and two known species of the Genus Tylencholaimellus Cobb in M. V. Cobb, 1915 (Nematoda: Dorylaimida: Tylencholaimoidea). 15 records from Inventaire participatif des rhopalocères de Bois-Guillaume, Bihorel et Isneauville. 439 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 46201 records from MDFRC macroinvertebrate survey. 25507 records from HBRG Fungus, Lichen & Lower Plants Dataset. 62 records from Amtsrain Apolda-Zottelstedt. 136 records from Inventaire des reptiles 2014 pour les Atlas communaux de la Biodiversité du PNRLG. 8 records from Mamíferos de un Área Degradada por Actividad Minera en la Costa Caucana. 175 records from Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 9 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0001A. 17229 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 121 records from Owere Fiddel. 31 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 16 records from Ensemble des données récoltées par le CD40 dans le cadre de la compensation Vison sur la commune de l'AIRE-SUR-L'ADOUR. 57 records from Données de la Réserve Naturelle Régionale du Marais de Larchant provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 2003 records from Cladocera distribution updates 2014. 255 records from AGIR_Ecologique_2017_12_18. 2001 records from Données naturalistes de Nicolas LOEUILLE. 1 records from Revision of the Agrilus purpurifrons species-group (Coleoptera, Buprestidae, Agrilinae). 20487 records from Inventaire de la flore de Charente-Maritime 2017. 320 records from The Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 36 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 7676 records from Données naturalistes de Cyril EPICOCO. 99 records from Dorfrand Mauderode. 6 records from Neoplecostomus canastra, a new catfish (Teleostei: Siluriformes) species from upper Rio Paraná basin. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 56 records from Shrews of Poland. 2 records from New species and new records of predaceous midges in the genera, Schizonyxhelea Clastrier and Stilobezzia Kieffer from Mexico (Diptera: Ceratopogonidae). 122 records from Scottish Beaver Trial incidental species records. 3692 records from K-State Museum of Entomological and Prairie Arthropod Research. 2 records from Neotype designation for Rhinogobius carpenteri Seale 1910, and its placement in Tukugobius Herre 1927 (Teleostei: Gobiidae). 4 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 6069 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 29 records from STELI 2015 Saint-Pée-sur-Nivelle (64) par l'association EcoGIS. 100672 records from Vulnerable marine ecosystems in the South Pacific Ocean region. 82 records from BIRDRACE Die Ziegeneier. 683 records from Diversidad y distribución geográfica de las especies de culícidos de importancia médica en la región centro-occidental de México. 5229 records from European Moth Nights. 1 records from New Species of Blindsnakes (Squamata: Gerrhopilidae) from the offshore islands of Papua New Guinea. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 4476 records from Benham Rise 16S raw sequence reads. 6804 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 11 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 261 records from Inventaire 3B initié par l'Université de Bordeaux 2012 / 2014. 2056 records from Données d'invertébrés récoltées pour l'étude des GPSO. 492 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 67938 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 438 records from Microbial Culture Collection, National Institute for Environmental Studies. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 931 records from Données naturalistes de Mathilde DUSACQ. 1705 records from 16S rDNA metagenomes of Western Balkans glacial lakes sediments. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 3 records from Four new species and new records of Atopsyche Banks (Trichoptera: Hydrobiosidae) from Pantepui biogeographical region (Venezuela). 56020 records from Données Vigie-Flore. 58769 records from Vascular Plant Specimen database of Kanagawa Prefectural Museum of Natural History. 346 records from Birds and plant species near Petushki town (Vladimir region). 41309 records from Données naturalistes de Monsieur François FOURNIER. 444 records from Phenology of Crocus. 1587 records from TWIC Record a Raptor Survey. 1 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 74 records from Schulwald Grundschule Brügge. 1 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 958 records from Epifitas del piedemonte de Yopal. 9 records from Jeu de données convention FEGVE-SPN (numéro 2). 30011 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 4 records from Molecular study supports the position of the New Zealand endemic genus Lamellomorpha in the family Vulcanellidae (Porifera, Demospongiae, Tetractinellida), with the description of three new species. 2 records from Pseudanthias emma new species, with notes on a collection of anthiadine serranid fishes from off Myanmar (eastern Indian Ocean). 549 records from Bryophytes specimens of Akita Prefectural Museum. 81 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 57313 records from Online Atlas of Vascular Plants 2012-2020. 154 records from Shannon Index and species richness for arthropods. 819 records from Millenium Seedbank (MSB). 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 67 records from Área Las Hermosas - Cantidad area ocupada oso, 2018. 15248 records from Colección de Peces del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 1920 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from Revision of the Diplommatinidae (Gastropoda: Cyclophoroidea) from Java. 27673 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 468 records from Phenological Center - Plants (Laplandskiy). 16 records from Crustacea ZMK. 92 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 10 records from Results of foraminifer and ostracode analyses of Hole 302-M0002A. 455 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 1 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 2868 records from ICEL (Land - Invertebrates). 3870 records from UTEP Herpetology (Arctos). 3402 records from Biological Reference Collections ICM CSIC. 2 records from First Record of Dericorys albidula Serville, 1838 (Orthoptera: Dericorythidae) in Tunisia and Libya. 43 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 381 records from Coléoptères Silphidés du département du Loiret. 1178 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 2946 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 322295 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 104 records from Urwald 1 (Bad Waldsee). 31152 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 1 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 122 records from Birdrace-Hügelland-Mainz/Bingen. 16 records from Hazel Dormouse in Ireland. 6 records from Description of a new Aemene Walker, 1854 from North Thailand and Myanmar, with a checklist of the genus (Lepidoptera, Erebidae, Arctiinae). 14 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 1116 records from Colección de Bruniales, Buxales, Canellales y Caryophyllales del Museo Botánico CORD - IMBIV. 381 records from Agroforestry plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 6 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 6 records from Revision of the Ulopinae leafhoppers (Hemiptera: Cicadellidae) of the Indian subcontinent, I. Ulopini genera: Daimachus, Radhades and Ulopsina. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 43421 records from Insects, Outer Hebrides. 1 records from A new species and a key to world species of the flavipes species-group of the genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) from Japan. 220 records from Mammals in MZNA-VERT: project Loza. 46 records from An der Ohm, (Wettsaasen). 49 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 185 records from Inventaire des odonates d'intérêt communautaire Midouze 2005. 1 records from New species of the snakefly genus Mongoloraphidia (Raphidioptera: Raphidiidae) from China. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 5725 records from BioGIS - Vascular plants - Israeli Gene Bank. 13 records from Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (III). 2418 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 7 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 16143 records from marine metagenome Metagenome. 13 records from Sea Education Association Sargasso Sea Cruise C247 May 2013. 1231 records from Invertebrates (except insects), Outer Hebrides. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 31457 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 1 records from E. C. Smith Herbarium (ACAD) - Cape Breton University Collection. 2 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 179 records from Ictiofauna de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 62 records from Sibojaï_2017_12_18. 2 records from A new species of rheophilic cyprinid fish (Teleostei: Cyprinidae) from the Brahmaputra Basin, northeast India. 893 records from DBRC Lutra lutra records 1952 - 2016. 32 records from New records for Albania based on taxa from the Prespa National Park. 1 records from Mammalians Specimens of Akita Prefectural Museum. 8394 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 26242 records from Abondances et caractéristiques biologiques des juvéniles de saumons échantillonnés lors des indices d'abondance du saumon dans la rivière Scorff (France). 1 records from Description of a new Oriental stonefly species, Phanoperla constanspina (Plecoptera: Perlidae) from Mindanao, Philippines and association of life stages using DNA barcoding. 2 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 934 records from Observations opportunistes de mammifères marins de l'observatoire PELAGIS. 21884 records from MSB Fish Collection (Arctos). 1 records from A New Species of Abbrosoga (Hemiptera: Fulgoroidea: Delphacidae), An Endemic Puerto Rican Planthopper Genus, with an Updated Checklist of the Delphacidae of Puerto Rico. 3399 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Gill Net. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 333 records from Langes Tannen (Uetersen). 754 records from Marine Turtles. 53 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 8 records from Aktion des Romain-Rolland-Gymnasiums. 258 records from Etude d'impact projet cluster des médias Jeux Olympiques. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 3 records from New species of oribatid mites of the family Oppiidae (Acari, Oribatida) from Chile. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 41249 records from Inventaire de la flore de Lot-et-Garonne 2016. 91 records from Chronicle of Nature - Phenology of Fishes of Sikhote-Alin State Nature Biosphere Reserve Named After K. G. Abramov. 52 records from Anfibios presentes en las lagunas del municipio del Medio Baudó. 327 records from VIT Herbarium - Mycotheca (The Natural History Museum of Álava). 6 records from Vermont Orthoptera Records from Historic Dot Maps. 1 records from First description of the male of the eyeless spider Draconarius tortus Chen, Zhu & Kim 2008 from China (Araneae: Agelenidae: Coelotinae). 12 records from A new species and new records of Oocyclus Sharp, 1882 (Coleoptera: Hydrophilidae) from Brazil. 356 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 571 records from Cuxhavener Küstenheiden. 665 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 346 records from UWYMV Bird Collection (Arctos). 1463900 records from Hatikka Observation Database. 25 records from Données naturalistes de Monsieur JOURDE Rémi. 5402 records from inatura - Erlebnis Naturschau Dornbirn. 21 records from CAS Entomology Type (TYPE). 14 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 1787 records from North East Scotland Amphibians & Reptiles 1850 - 2016. 5669 records from MBML-Anfibios - Coleção de Anfíbios MBML. 119 records from Kinorhyncha. 615 records from Marine subseafloor sediment Targeted Locus (Loci). 217 records from Dataset of herbarium specimens of threatened vascular plants in Catalonia. 990575 records from PlutoF platform observations. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 2 records from The Oncometopia orbona species group (Hemiptera, Cicadellidae, Proconiini). 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 78679 records from Nutrient addition mesocosm experiment Targeted Locus (Loci). 249 records from CHAS Ornithology (Arctos). 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 4960 records from RNF - Données de l'Association GEREPI (GEstion de la REserve naturelle nationale du PInail). 95 records from Megafauna of the UKSRL exploration contract area and eastern Clarion-Clipperton Zone in the Pacific Ocean: Annelida, Arthropoda, Bryozoa, Chordata, Ctenophora, Mollusca. 238 records from Données Mammifères marins Aquasearch - Dauphin Passion. 1 records from A new blind snake of the genus Letheobia (Serpentes: Typhlopidae) from Rwanda with redescriptions of L. gracilis (Sternfeld, 1910) and L. graueri (Sternfeld, 1912) and the introduction of a non-invasive preparation procedure for scanning electron microscopy in zoology. 2 records from New data of Nazeris Fauvel in Xizang, China (Coleoptera, Staphylinidae, Paederinae). 1 records from Taxonomic updates for some confusing Micronesian species of Camponotus (Hymenoptera: Formicidae: Formicinae). 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 3 records from Two new species and key to the salina group of the genus Rhagovelia Mayr, 1865 (Hemiptera: Heteroptera: Veliidae) from Colombia. 15 records from Nematoda of Costa Rica (INBio). 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 1 records from A new Puddle Frog, genus Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae), from the eastern part of the Upper Guinea biodiversity hotspot, West Africa. 4 records from Description of four new species of the Cirolana ‘ parva group’ (Crustacea: Isopoda: Cirolanidae) from Thailand, with supporting molecular (COI) data. 2135 records from Amphibian and reptile records for Great Britain 2016-2017. 8 records from Chronicle of Nature - Phenology of Amphibia of Visimsky Nature Biosphere Reserve. 3 records from Three new species of the Stenus cephalotes group fom Zhejiang, East China (Coleoptera, Staphylinidae). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 1582 records from WTSWW Data: All Taxa (West Wales). 5704 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 262796 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 482 records from Kühmark bei Wetzlar. 192 records from "Ahrschleife bei Altenahr". 7 records from Revision of the Madagascan genera Oncodopus Brongniart and Colossopus Saussure (Orthoptera: Tettigoniidae: Conocephalinae; Euconchophorini), with description of Malagasopus gen. nov.. 295 records from Enriched mixed culture from mangrove sediment with capability of producing 1,3-PDO from glycerol genome sequencing and assembly. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 12 records from A new Bifidocoelotes species, with the description of the male of B. primus from Hong Kong, China (Agelenidae: Coelotinae). 45 records from La familia Asclepiadaceae en México. 7 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 523 records from Colección de Rosales, Salviniales, Santalales, Sapindales, Saxifragales, Schizaeales y Selaginellales del Museo Botánico CORD - IMBIV. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 16 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 368 records from Otter survey of Ireland 2004 & 2005. 17487 records from Chronicle of Nature - Phenology of Plants of FSE Zapovednoe Podlemorye. 13 records from Diversity and population densities of coraciiform birds in Zambezi riparian forest. 17 records from Six new species of Otacilia from southern China (Araneae: Phrurolithidae). 124 records from Birdrace-LohmannsAdleraugen-Münster. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 3 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 249801 records from All taxa records for Leicestershire and Rutland. 1232 records from GEN_TEREO_2017_12_18. 130 records from Données naturalistes de NOËL Rémi. 1 records from La Côte oubliée - La Planète Revisitée - Nouvelle-Calédonie 2017. 2 records from Sinibotia lani, a new species of botiid loach (Teleostei: Botiidae) from Guangxi, China. 91 records from Donación de la base de datos del Dr. Ortega Paczka resultados de la computarización de datos de colecta de muestras de maíz y otros cultivos asociados de diferentes regiones de México. 1854 records from Microbial diversity in shallow water hydrothermal sediments of Gueishan Island, Taiwan. 23 records from Landwehrbach. 464 records from Bocachico Prochilodus magdalenae (Characiformes: Prochilodontidae) en la cuenca media y baja del río Magdalena. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 1 records from Données naturalistes de Mathieu REVEILLAS. 766 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé en 2014 et 2015. 516 records from Ims fish tag database. 295 records from Données de VINCENT Alexis (SAPROX). 39 records from Regenrückhaltebecken Bad Bevensen. 1721 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1100 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 10 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 8 records from The first record of Gnathostenetroididea Kussakin, 1967 from Australian waters with description of four new species of Gnathostenetroides Amar, 1957 (Crustacea: Isopoda: Asellota) from the Great Barrier Reef. 8 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Insectarium René-Martineau (IRM). 2186 records from Inventaire éclair de Natureparif - Année 2015. 544 records from Vascular plants from a study of primary producer traits across an altitudinal gradient in alpine Finse. 23 records from Herbarium of Shinshu University. 788 records from University Of Pretoria: Lacewing Database Project (1911-2015). 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 386 records from USAC Mammals Collection. 47952 records from Tour_du_Valat_2017_12_18. 7442 records from KUBI Herpetology Collection. 1 records from The uncommon Neotropical genus Pazius Navás, 1913 (Mecoptera: Bittacidae): a comprehensive synthesis, with description of a new Brazilian species. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 11 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 981 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 2 records from Two new species of Biantes from China and Malaysia (Opiliones: Laniatores: Biantidae). 735 records from Données naturalistes de Bernard Lalanne-Cassou. 51 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 34760 records from Données naturalistes de Xavier CUCHERAT. 6 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 30 records from BioGIS - Mammals - SPNI. 18 records from Revision of the enigmatic Southeast Asian spider genus Savarna (Araneae, Pholcidae). 5 records from The discovery of Rock Geckos Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) in the Tanintharyi Region, Myanmar with the description of two new species. 12 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 17518 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 90159 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 147 records from The genus Tarsonemus Canestrini and Fanzago, 1876 (Acari: Heterostigmatina: Tarsonemidae) in East Azerbaijan, Iran, with a description of T. lenticulatus sp. nov. and re-description of T. annotatus Livshits, Mitrofanov and Sharonov, 1979. 6873 records from Monitoring of the intertidal biodiversity of rocky beaches with schools in Portugal 2005-2010. 5 records from Gergithoides Schumacher, 1915 in Vietnam, with two new species, and taxonomic notes on the genus (Hemiptera: Fulgoromorpha: Issidae). 767669 records from SEWBReC Birds (South East Wales). 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 807 records from Área Galeras - Monitoreo de Aves, 2016. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 1030 records from MEXU/Asteraceae. 1 records from Collection Echinodermata SMF. 607 records from Living coccolithophores from the Gulf of Sirte during the summer of 2008. 4 records from A new species of large-bodied, tuberculate Hemidactylus Oken (Squamata: Gekkonidae) from the Eastern Ghats, India. 5017 records from Colección Entomológica del Programa de Biología - Universidad de Caldas (CEBUC). 684 records from Estudio de la diversidad genética y su distribución de los maíces criollos y sus parientes silvestres en Michoacán. 1 records from Geographically structured genetic variation in Ptychozoon lionotum (Squamata: Gekkonidae) and a new species from an isolated volcano in Myanmar. 2062 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 7384 records from Phytoplankton Species Composition, Abundance and Cell Size in San Francisco Bay: Microscopic Analyses of USGS Samples Collected 1992-2014. 570 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 4 records from Pseudonemesia tabiskey, a new species of Pseudonemesia Caporiacco 1955 and new ultramorphological data for the Microstigmatinae (Araneae: Microstigmatidae). 1 records from A new species of the mud shrimp genus Axianassa Schmitt, 1924 (Decapoda: Gebiidea: Laomediidae) from the Ryukyu Islands, southern Japan. 2059 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 3 records from Channa aurantipectoralis, a new species of snakehead from Mizoram, north-eastern India (Teleostei: Channidae). 10693 records from Arizona State University Hasbrouck Insect Collection. 2536 records from Invasive Alien Species Occurrence in Ghana. 175 records from Enquête Laineuse du Prunellier (OPIE). 2 records from Taxonomic review of Dendrophryniscus brevipollicatus Jiménez de la Espada, 1870, with revalidation of D. imitator (Miranda-Ribeiro, 1920) and D. lauroi Miranda-Ribeiro, 1926, and description of four new related species (Anura, Bufonidae). 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 1250 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 29 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 1 records from Taxonomic revision of the genus Hirotophora Brown et al. (Diptera: Phoridae) with the description of a new species from Chile. 11 records from BID-AF2015-0004-NAC Collection de Diptères du LEA-UL. 4 records from Two species of Ceradocus collected from coastal areas in Japan, with description of a new species (Crustacea: Amphipoda: Maeridae). 448 records from Données araignées de Corse par Canard A., Rollard C., Villepoux O.. 309 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 14385 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 54 records from MEXU/Flora de Oaxaca. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 2132 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 9743 records from marine sediment metagenome Raw sequence reads. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 1 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 10005 records from Amphibiens et Reptiles de France (Enquête 2). 2131 records from Dolichopodidae of Portugal - dataset 2009-2018. 3158 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 857 records from Colección Hidrobiológica del Chocó. 70 records from Données du naturaliste Mael Garrin. 1094 records from Données naturalistes de Christophe HANOT. 960 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE255. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 2780 records from Données naturalistes d'Alain BERLY. 1986 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 9 records from Two New Liocranid Species Records From Turkey (Araneae: Liocranidae). 22 records from Données opportunistes récoltées par le Département des Landes jusqu'en 2015. 23 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 946 records from Red-throated diver national surveys in Scotland - raw data. 129 records from Inventaire et regroupement de données Natura 2000 Midou-Ludon 2012. 11714 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 77 records from Suivi naturaliste du Parc du Peuple de l'Herbe. 146782 records from Données de la flore d’Alsace (SBA). 20 records from Collection Aves (bird skeletons) SMF. 31 records from The Plecoptera of Panama. III. The genus Anacroneuria (Plecoptera: Perlidae) in Panama’s national parks: 2017 survey results. 738 records from Étude biodiversité toitures végétalisées d'Île-de-France réalisée par Natureparif / ARB. 5 records from Literature based species occurrence data of birds of North-East India. 56 records from Données du/de la naturaliste Goncalves Cristina provenant de la base de donnée du SINP Île-de-France CETTIA. 1765 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 35 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2 records from Description of three new species of Encyrtidae Walker (Hymenoptera: Chalcidoidea) from India. 696 records from the diversity of anammox bacteria in the subterranean estuary. 23567 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 141 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 2313 records from Données du naturaliste Maillard Bernard provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Two new species of Rhopalopsole (Plecoptera: Leuctridae) from China. 1139 records from SWECO. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1 records from Taxonomic review of Stictophaula (Orthoptera: Phaneropterinae) with the description of one new species from Brunei Darussalam. 635 records from Pseudoscorpion Recording Scheme of the UK. 11115 records from EAC - Herbário Prisco Bezerra. 39 records from Suivi des reptiles en forêt du Madrillet. 2109 records from East Ayrshire Species Database. 232 records from Flora (vascular) y fauna (aves) de los Parques Nacionales del estado de Baja California: Constitución de 1857 y Sierra San Pedro Mártir. 11163 records from Données du naturaliste DEHALLEUX Axel provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Type material housed in the Carcinological Collection of the Museo de La Plata, Argentina. 8739 records from Insect Collection of the Laboratory of Applied Entomology of the Faculty of Sciences of the University of Lome. 83 records from Phytoplankton abundance at station Rigel_3_2005-02 in Febraury 2005, Chipana, Chile. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 2 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 1801 records from Olga Lakela Herbarium, University of Minnesota Duluth. 1 records from A cryptic new species of hummingbird of the Campylopterus largipennis complex (Aves: Trochilidae). 136 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (3), 2012 - Données faune. 44 records from Leegmoor (Moormerland/Leer). 34 records from Earthworms population in old-growth taiga forests of Pechoro-Ilych State Nature Reserve. 651 records from Collection Crustacea - ZMB. 423 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 6 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 5625 records from Données Rhopalocères PNRLG. 1 records from The crab spider genus Tarrocanus Simon, 1895 with notes on the genera Alcimochthes Simon, 1895 and Domatha Simon, 1895 (Araneae: Thomisidae). 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 918 records from Actualización de la base de datos computarizada de la colección ictiológica de la Universidad Autónoma de Baja California. 752 records from Illumina high-throughput sequencing of bacterial community. 2 records from Schistura epixenos, a new species of loach from the Nakai Plateau, Laos (Teleostei: Nemacheilidae). 110 records from Insectos del páramo de Sumapaz, Cundinamarca - Proyecto Colombia Bio. 163 records from Données opportunistes de Mammifères marins SPM de 1997 à 2007 récoltées par le RNE et le Baleineau de SPM de 1997 à 2007. 6 records from Distribution of two species of Nephropsis Wood-Mason, 1872 (Crustacea, Decapoda, Nephropidae) from northeastern Brazil. 100 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 50 records from Données naturalistes de Maxime BEAUJEON. 5782 records from microbial diversity Raw sequence reads. 21 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 26 records from On some new or rare spider species from Lesbos, Greece (Araneae: Agelenidae, Amaurobiidae, Corinnidae, Gnaphosidae, Liocranidae). 8 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 4 records from First records of Kempnyia and Macrogynoplax (Plecoptera: Perlidae) from Tocantins State, Brazil with description of the immatures and the adult female. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 39 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 61 records from Ibaraki Nature Museum, Birds collection. 10526 records from Waterway Survey. 8 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 4426614 records from Great Backyard Bird Count. 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 13 records from Warnowufer Groß Klein. 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 2658 records from Living Collection of the Gothenburg Botanical Garden. 3630 records from Mollusca collection of National Museum of Nature and Science. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 10486 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 24 records from Peces de la expedición en el páramo de Ocetá, Boyacá - Proyecto Boyacá BIO. 360 records from Chronicle of Nature - Phenology of Mammals of State Nature Reserve Olekminsky. 679 records from Monitoreo y seguimiento de fauna silvestre terrestre para el AID y AII de la Central Hidráulica Cucuana. 2018-IIS. 875 records from Leicestershire and Rutland Mature trees Inventory 2011. 11 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 10 records from Valentin Moser Bats. 39 records from Soolbach-Tal. 92 records from Planktonic bacterial communities in the arctic Canada Basin and Kongsfjorden. 521 records from Bayerische Donau - Leipheim. 238 records from Données du naturaliste Jérôme Hanol. 187371 records from NMNH Extant Specimen Records. 4 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 52443 records from Extracellular DNA marine sediment Targeted Locus (Loci). 54 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 12947 records from Sediment of acid mine drainage Targeted loci environmental. 285 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 384 records from "Schwarzwassertal" bei Pobershau. 7 records from Taxonomic revision of a darkling beetles genus Anaxius (Tenebrionidae: Pedinini: Helopinina). 325 records from Données de la structure OGE (Office de Génie Ecologique) provenant de la base de donnée du SINP Île-de-France CETTIA. 2340 records from marine metagenome Targeted Locus (Loci). 264 records from Plan de vertebrados de la Patagonia. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 39496 records from South Australian Museum Australia provider for OZCAM. 1 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 843 records from A crowdsourcing approach to collecting photo-based insect and plant observation records. 1 records from Brock University Herbarium (BU). 1 records from Description of the last stadium larva of Erythrodiplax abjecta (Anisoptera: Libellulidae) from the eastern Colombian Andes. 23 records from Mains of Kinblethmont Solar Park Amphibian Records 2014. 3841 records from Whicher Scarp Flora Survey. 28 records from Données naturalistes de Cédric POUCHARD. 69 records from Unter hellen Zinnen und finsteren Grotten. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 95 records from Elasmobranquios de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 273 records from Données espèces - Expertise IQE 119. 2 records from New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China. 1 records from herbarium_database. 1 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6304 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from A new species of the emesine assassin bug genus Emesopsis (Hemiptera: Heteroptera: Reduviidae) from Vietnam. 18 records from Monocotyledonous Geophytes of Fergana Valley. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 2693 records from Grand Voyeux - Suivis scientifiques. 42 records from UWIZM Cnidarians. 17 records from New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil. 3 records from A new species of the spider genus Solenysa from China (Araneae, Linyphiidae). 1316 records from Recurso hidrobiológico de los manglares de la Zona de Uso Sostenible de la Balsa (ZUSLB) y la Zona de Recuperación de Tinajones (ZRT). 100 records from Taiwan Forestry Research Institute. 92 records from A list of coleoptera recorded in Mixed Forest habitat in Arabuko-Sokoke Forest, Kenya. 1480 records from DIPOL. 1395 records from Colección Zoológica de la Universidad del Tolima (CZUT)- Mastozoología. 58669 records from Tasmanian Museum and Art Gallery provider for OZCAM. 538 records from UAM Invertebrate Collection (Arctos). 1836 records from Données de la structure Fédération 77 de Pêche et Protection du Milieu aquatique provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Diglotta mersa (Haliday) and Halobrecta flavipes Thomson, two new species for the Canadian fauna (Coleoptera, Staphylinidae, Aleocharinae). 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 11 records from Chronicle of Nature - Phenology of Amphibia of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 4579 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 348 records from SNH Invertebrate Site Condition Monitoring 2013/14: Black Wood of Rannoch SSSI. 410 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 170 records from Revision of Anisepyris Kieffer (Hymenoptera, Bethylidae), with description of 135 new species. 1 records from First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae). 3 records from Three new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 9 records from Three new taxa of the genus Cechetra Zolotuhin & Ryabov, 2012 (Lepidoptera, Sphingidae) from South-East Asia with notes on other species of the genus. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 58 records from ABBBS Bird Banding records from the Australian Antarctic Territory and Heard Island.. 2 records from Description of Two New Species of Baeocera Erichson (Coleoptera: Staphylinidae: Scaphidiinae) from México. 6 records from New State and Host Records for Agromyzidae (Diptera) in the United States, with the Description of Ten New Species. 65490 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Two new species of comb-clawed beetles (Coleoptera: Tenebrionidae: Alleculinae) from Yunnan, China. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 3737 records from Inventaire des pelouses calcicoles du PNR du Marais Poitevin 2017. 58 records from Golf de Chantilly. 432 records from Automatic acoustic Monitoring and Inventoring of BIODiversity. 1 records from Two new species of the bamboo-feeding planthopper genus Arcofacies Muir (Hemiptera: Fulgoroidea: Delphacidae) from China. 227 records from Data on cetacean strandings (1999 - 2014) on the Ukrainian coast of the Black Sea and the Sea of Azov and adjoining areas. 12 records from Revision of the genus Doryscus Jacoby (Coleoptera: Chrysomelidae: Galerucinae). 16264 records from Patagonian fjord prokaryote community. 9 records from New species and records of Cladiopsocus Roesler (Psocodea: ‘ Psocoptera’: Psocomorpha: Cladiopsocidae) from Colombia. 59 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1738 records from Registros Primates Neotropicales Convocatoria APC. 84 records from Herpetile collection NTNU University Museum. 631 records from Anammox bacteria in sediment cores of Daya Bay, China. 2980 records from Colección de Peces Universidad Católica de Oriente. 1861 records from Données du naturaliste DELAPRE Jean-Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 759 records from Fitoplancton marino frente a Baja California. 2. Áreas de surgencias de la región Ensenadense. 4 records from Two new species of Oxynoemacheilus from the Tigris drainage in Iraqi Kurdistan (Teleostei: Nemacheilidae). 215 records from Aves de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 1 records from A taxonomic revision of the genus Thalia Blumenbach, 1798; Weelia Yount, 1954; Brooksia Metcalf, 1918 (Salpida: Salpidae) from East Coast of Peninsular Malaysia. 1522 records from marine sediment metagenome Raw sequence reads. 2 records from Two new species of Podonomus Philippi (Diptera: Chironomidae: Podonominae) from mountains of Southeastern Brazil. 402 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE272. 469 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 111 records from Birdrace-Uhulogen-Lippe. 373 records from Bird Banding Data for Black Rock Lodge, Belize 2016-2018. 221 records from Jervois and Karinga Flora. 1170 records from Springtales from lichen communities at Kollåsen in Norway. 1491 records from Données du naturaliste ROUDIE Gilbert provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 3 records from Descriptions of species of Acrobeles von Linstow, 1877 (Nematoda, Rhabditida, Cephalobidae) from Kelso Dunes, Mojave National Preserve, California, USA. 21 records from Données naturalistes de Nathalie POT. 297305 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 2058 records from Données naturalistes de Julien BRISSET. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 69 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 12948 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 64 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 147 records from Observation records of Amphibians. 661 records from Targeting a portion of central European spider diversity for permanent preservation. 79 records from Mushroom Diversity of Cross River National Park Akamkpa Nigeria - Flora Database of University of Calabar. 154 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 298 records from Implementación del programa de monitoreo del cocodrilo del pantano (Crocodylus moreletti) México-Belice-Guatemala: región de coordinación MXRC2-Golfo Centro, Veracruz centro y norte Oaxaca. 4031 records from Census of species recorded during phytosociological surveys in Benin. 6977 records from 2019_NSMK_PL_2. 12208 records from SEAPOP - Last observation per locality in winter season. 18 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 485 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 804 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 127 records from Inventory of Bonou, Kilibo and Lama forests (South and centre Benin). 125 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 1146 records from Bryophytes, fungi and lichens on dead wood. 4 records from A new species of Ferorhinella (Hemiptera: Cercopidae) from southeastern Brazil with taxonomic notes on the genus. 150 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 1 records from Review of Cosmocomoidea (Hymenoptera: Mymaridae) from China, with descriptions of two new species. 50 records from Artensuche auf den Elbwiesen in Radebeul. 3472 records from Microhabitat distribution of arboreal oribatid mites (Oribatida), associated with the Siberian pine (Pinus sibirica) of Western Siberia.. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 33510 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 564 records from Collection Pisces SMF. 7964 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Bag Seine. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 5217 records from NZCS Brownsberg Nature Park Camera trap Monitoring 2013-2015. 12202 records from Pelagic Gulf of Mexico Targeted loci environmental. 2 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 2652 records from My naturesounds - nature observations with sound recordings. 1 records from Dolichochorus Strobl 1904: a valid genus of Mesochorinae (Hymenoptera: Ichneumonidae: Mesochorinae). 547 records from arthropods on Plantago lanceolata. 24 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 4495 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 53 records from Observations de Rhopalocères récoltées par l'association ECOGIS dans le cadre de ses missions. 2 records from A new genus of Tetracampidae (Hymenoptera) from South Africa. 2 records from A new Subleuconycta (Lepidoptera: Noctuidae: Acronictinae) species from Taiwan. 372 records from Carabidae of the European North-East of Russia. 118 records from Invertebrate collection of University of Oulu Zoological Museum. 708 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 813 records from Tejidos colectados en la expedición al municipio Cimitarra, Santander - Proyecto Santander BIO. 11997 records from University of New Mexico Herbarium. 259 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 1040 records from Données de l'Association naturaliste d'étude et de protection des écosystèmes CAUDALIS 2015 Chiroptères, Maculinea, Cistude d'Europe. 2204 records from Données naturalistes d'Anaïs MAS. 1620 records from Aldegondabreen cryoconite Targeted Locus. 1057 records from Palynological analysis of sediment core GeoB9508-5. 91 records from Données de la naturaliste Estelle Duchemann. 1 records from Description of the mature larva and pupa of Ora semibrunnea Pic (Coleoptera: Scirtidae) with notes on its biology. 5 records from Cryptic species in the nuisance midge Polypedilum nubifer (Skuse) (Diptera: Chironomidae) and the status of Tripedilum Kieffer. 7282 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 15 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from COR herbarium - Universidade Federal de Mato Grosso do Sul / Campus Pantanal - Herbário Virtual Reflora. 177 records from Suivi temporel des Rhopalocères 2016. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 1897 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 85 records from New findings of the butterfly Phengaris teleius at the border between Hungary and Serbia (Lepidoptera: Lycaenidae). 921840 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 78193 records from sediment metagenome Raw sequence reads. 10078 records from NCSM Herpetology Collection. 69 records from Bishop's University Insect Collection (BUIC). 3 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 5330 records from Environment Agency England and Wales (2007) freshwater invertebrate species (single species families). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 10665 records from HURB - Herbário do Recôncavo da Bahia. 24 records from Chameleonfishes in Bangladesh: hipshot taxonomy, sibling species, elusive species, and limits of species delimitation (Teleostei: Badidae). 2 records from Taxonomic revision of Brasiloniscus (Oniscidea, Pudeoniscidae) with description of a new species. 5350 records from Sediment metagenome. 4109 records from SEWBReC Myriapods, Isopods, and allied species (South East Wales). 34 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 412638 records from BioFokus. 10932 records from Données lichens de l'ATBI Parc National du Mercantour / Parco Naturale Alpi Marittime. 15253 records from Anymals+plants - Citizen Science Data. 20 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area II. 54 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 14 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 7598 records from données araneologiques de TOURNEUR Jérôme et CPIE Loire-Anjou. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 1 records from Orthotrichum dentatum T. Kiebacher & Lüth sp. nov. (Orthotrichaceae). 991 records from Données du/de la naturaliste CARON Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from A new species of the catfish genus Cordylancistrus (Siluriformes, Loricariidae) from the Sierra Nevada de Santa Marta, Colombia. 5494 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 771 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 498 records from 13C methanol SIP (WCO station L4). 82 records from CNAN/Scorpiones. 6271 records from Tetraonid line transect surveys from Norway: Data from Finnmarkseiendommen (FeFo). 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 5 records from Données naturalistes de Pascal ROUSSE. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 184 records from Vaste étude d'impact sur la biodiversité de la bassée commanditée par EPTB dans le cadre de réalisation de casiers anti crues. 5 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 6 records from Description of five new species of the genus Stigmaeus Koch (Acari: Raphignathoidea: Stigmaeidae) from Turkey. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 2 records from A taxonomic study of Eupolyphaga Chopard, 1929 (Blattodea: Corydiidae: Corydiinae). 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 2 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 16 records from Two new species of Hoplonannus (Heteroptera: Schizopteridae: Schizopterinae) from the Brazilian Amazon. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 2 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 83 records from City of Edinburgh Natural Heritage Service - General Public Records.. 664 records from MEXU/Colección de Briofitas. 1183 records from Cepario del Laboratorio de Microbiología y Mutagénesis Ambiental de la UIS (LMMA). 4245 records from Datos observacionales sobre biodiversidad Ministerio del Medio Ambiente 2015. 1 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 1 records from A new species of the genus Mongolotettix Rehn, 1928 from Hubei, China (Acrididae, Acridoidea, Orthoptera). 27 records from Tortugas marinas de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 402 records from Cybelle Méditerranée. Observation nautique avec effort d'observation. 151 records from BIRDRACE Birding Bentheim. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 197 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 1924 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 41 records from Western Australian Seabirds. 22018 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 79 records from Données opportunistes sur les rhopalocères récoltées par les agents de la RNN entre 1997 et 2015. 3979 records from Données naturalistes de Loïc SALAUN. 243 records from Thistles species and abundance. 85 records from Área Galeras - Estructura Palma (Geonoma undata), 2016. 1749996 records from Finnish Floristic Database (Finnish Museum of Natural History Collections). 105 records from Données aranéologique de HENRARD Arnaud. 2851 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 1 records from A new species of the genus Calambus C. G. Thomson, 1859 (Coleoptera: Elateridae: Dendrometrinae) from China, with notes on the other species of the genus of the East Palaearctic region. 1 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 2 records from Two new species of Sochinsogonia (Hemiptera: Cicadellidae: Cicadellinae) from Philippines. 10 records from Caracterizacion Ecologica de la Fauna de Anfibios Presentes en la Zona de Influencia de la Parte Alta del Rio Guangui. 2 records from The Xiphydria palaeanarctica group from Japan (Hymenoptera, Xiphydriidae). 12 records from A new genus and two new species of miniature clingfishes from temperate southern Australia (Teleostei, Gobiesocidae). 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 874 records from Données naturalistes de Monsieur DAMOISEAU Sébastien. 134 records from On the spider genus Cryptachaea from Peru, Bolivia and cave environments in Brazil: a new species, additional descriptions and new records (Araneae, Theridiidae). 191 records from ABC Mungolwe Hills, Machinga Sampling Event data. 814 records from flower availability 2008 Hainich. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 1 records from Données naturalistes de Stéphane ORIO. 651 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 5692 records from Andes to Amazon Biodiversity Program. 265 records from 16S rRNA gene (V2-V3 region) based analysis of soil procaryotic community composition, Alb VIPs 2008. 60 records from Suivi botanique et entomologique pour la gestion de la portée de RTE sur l'emprise de la RNN de Bassée. 244 records from WildesMoor bei Schwabstedt. 288 records from Inventario herpetofaunístico del noroeste de Hidalgo. 2 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 296 records from Colección de Mamíferos - Universidad del Quindío. 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 164 records from Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 2 records from Persescaphium pari new genus and species, with an overview of Iranian Scaphidiinae (Coleoptera, Staphylinidae). 2 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 2 records from Revision of the genus Amazunculus Rafael (Diptera: Pipunculidae), with description of six new species. 18 records from Données naturalistes de ANDY PAPACOTSIA. 68 records from Données 2016 de la Réserve Naturelle Nationale de Chérine (36) située en Brenne, dans le département de l'Indre: Butor étoilé, Guifettes, Busard des roseaux et Cistude. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 466 records from Collection Ornithologie - SNSD. 13 records from Suivi de la reproduction des Lamproies de Planer sur les sites Natura 2000 en Seine-et-Marne. 7 records from A revision of the genus Eutetrapha Bates (Coleoptera: Cerambycidae: Lamiinae: Saperdini). 1 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 2138 records from Jardín Botánico Atlántico, Gijón: JBAG. 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 1 records from Larva of one of the world’s rarest and most threatened damselflies: Spesbona angusta (Odonata: Platycnemididae). 79874 records from 16S Amplicon Data from an Antarctic Cold Seep. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 1270 records from EDP Foz Tua: Amphibians - Complementary Studies [2009-2010]. 5 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 225 records from Inventaire des odonates 2014 pour les Atlas communaux de la Biodiversité du PNRLG. 7 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 62 records from Universitat de Girona: HGI-Cormophyta. 2 records from Molecular phylogeny of Hiptage (Malpighiaceae) reveals a new species from Southwest China. 38463 records from HO AVH data. 17702 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 4 records from Neotypification of Onuphis fukianensis Uschakov & Wu, 1962 and description of a new species of Onuphis (Annelida: Onuphidae) from China seas. 110 records from Données du Râle gris sur le territoire de la Guadeloupe. 5 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 24 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 84 records from Ober-Olmer Wald. 388 records from Desarrollo de una metodología para determinar la cobertura arrecifal en Areas Naturales Protegidas. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 4004 records from EDP Foz Tua: Amphibians - Ecological Monitoring Program [2010-2017]. 229 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 722 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 5401 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 13 records from Turf_Chronosequence_16S_ITS. 990 records from Bacterial communities from Thrombolites of Lake Sarmiento. 23761 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 261 records from Données espèces -expertise IQE 3. 134 records from BIRDRACE Griffin Wood Warblers. 154 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 2 records from On the sun-spiders of the ibirapemussu species-group of the genus Gaucha Mello-Leitão, 1924 (Solifugae, Mummuciidae), with description of a new species. 207114 records from Florida Keys Reef Visual Census 2005. 26 records from Phragmites of Canada. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 69 records from Mönchspark. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 24 records from Klosterwald Itzehoe. 4 records from A new species of Victrix Staudinger, 1879 from Kazakhstan (Lepidoptera, Noctuidae). 29 records from Berkeley subregion bats. 305 records from Données du naturaliste Arnaud Bak. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 1 records from Zorotypus huangi sp. nov. (Zoraptera: Zorotypidae) from Yunnan, southern China. 4 records from A new species of Versicorpus Deschodt, Davis & Scholtz, 2011 (Scarabaeidae Scarabaeinae: Byrrhidiini) from the Brandberg Mountain, Namibia. 3769 records from UCSC - Kenneth S. Norris Center for Natural History. 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 1235 records from Données naturalistes de Brice DEREPAS. 65 records from Contribution to the knowledge of the Nolini of the Maputo Special Reserve in South Mozambique with description of two new species and several taxonomic updates (Lepidoptera, Nolidae, Nolinae). 10213 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 1 records from Revision of the genus Bradyporus Charpentier, 1825 (Orthoptera: Tettigoniidae: Bradyporinae). 2 records from New records, taxonomic notes, and the description of a new species of Reduviidae (Hemiptera: Heteroptera) from Ecuador. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 2 records from A new species of Goniacerini from Cameroon (Coleoptera: Staphylinidae: Pselaphinae). 292 records from University of Tennessee Bryophyte Herbarium. 2662 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 247 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 58 records from Schulgarten Zinnowwald-GS. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 5170 records from Likona Invertebrates. 131 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 3 records from New sciaphilic plakinids (Porifera, Homoscleromorpha) from the Central-Western Pacific. 101 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 5417 records from Photodocumentation_of_Antarctic_Peninsula_Lichens. 18 records from Polysyncraton (Ascidiacea, Didemnidae): a re-examination of some specimens and descriptions of three new species. 15878 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 2 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 3 records from A revision of the clam shrimp Australimnadia Timms and Schwentner, 2012 (Crustacea: Spinicaudata: Limnadiidae) with two new species from Western Australia. 465 records from Philosophenwald und Wieseckaue in Gießen. 733 records from Colección de anfibios y reptiles del Laboratorio de Herpetología de la Universidad del Valle (UV-C). 21663 records from Tamborine Mountain Weekly Bird Observations. 4 records from Collection Myriapoda - SNSD. 38 records from BB-Biodiversität a. 3248 records from DBRC Hemiptera species records 1969 to 2015. 3 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 24659 records from Successional trajectories of coastal bacterioplankton communities in response to co-exposure of cadmium and phenanthrene. 15 records from New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean. 3523 records from NCSM Mammals Collection. 11 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 124 records from Umgebung der Elsa-Brändström-Schule (Krückaupark). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 16056 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 122 records from Inventaire de la Flore patrimoniale dans la RNN Etang de Saint-Paul avant le 31/12/2017. 2696 records from VIC - Herbário da Universidade Federal de Viçosa. 3 records from Contribution to the knowledge on the genus Barsine Walker, 1854 from mainland China and Indochina, with description of a new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 49466 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 125909 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 181 records from Hydraenidae of Madagascar (Insecta: Coleoptera). 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 2 records from A new species of the Gekko japonicus group (Squamata: Gekkonidae) from central Laos. 8787 records from Arctic Ocean Diversity. 6 records from New records, new genera, and new species in Acanthocinini (Lamiinae) from the Neotropical region, and new synonym in Cerambycinae (Coleoptera, Cerambycidae). 117427 records from Catch data from New Zealand research trawls since 2008. 1 records from Biotop Alexander-von-Humboldt-Schule. 2555 records from CASES2003_2004. 52 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 437 records from Données naturalistes de Jean-Michel LEMAIRE. 92 records from A second update to the checklist of Finnish long-legged flies (Diptera: Dolichopodidae), with a re-evaluation of the status of Hydrophorus callosoma Frey, 1915. 24071 records from Fife Nature Records Centre combined dataset. 652 records from Spider species diversity from wet and dry habitats. 49 records from CHAS Botany Collection (Arctos). 67 records from Berkeley subregion mammals. 85 records from Código de barras de diferentes grupos de peces mexicanos endémicos de la Mesa Central Mexicana. 9 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 5 records from A new species of Contarinia (Diptera: Cecidomyiidae) damaging inflorescence of Carya cathayensis (Juglandaceae) in China. 278 records from Investigación prioritaria hacia el conocimiento y conservación de tortugas amenazadas del bosque seco tropical colombiano Mesoclemmys dahli (Carrachina) y Chelonoidis carbonaria (Morrocoy). 8 records from Revision of Pyrrhalta (Coleoptera: Chrysomelidae: Galerucinae) species with maculate elytra. 125 records from Données d'occurrence de la flore du Sénégal (Acanthaceae - Chenopodiaceae), Herbier IFAN. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 1994 records from Amplicon-Based Illumina Sequencing Reveals High Diversity of Phytoplankton in the Coastal Waters of Qinhuangdao. 126 records from Données du naturaliste Calvel Dominique provenant de la base de donnée du SINP Île-de-France CETTIA. 12 records from Three new species of Seira Lubbock (Collembola, Entomobryidae, Seirinae) from Madagascar with Lepidocyrtus - like habitus. 20 records from Motzener Tonsee. 52 records from Données du/de la naturaliste RAMBAUD Maxime provenant de la base de donnée du SINP Île-de-France CETTIA. 270 records from BIRDRACE Niederlausitz-Team. 5 records from A review of the genus Paratus Simon (Araneae, Dionycha). 4 records from Four new species of tribe Coelidiini (Hemiptera: Cicadellidae: Coelidiinae) from the Afrotropical Region. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 2 records from Three new species of Calyptotheca (Bryozoa: Lanceoporidae) from the Great Barrier Reef, tropical Australia. 4074 records from SOPTOM_2017_12_18. 17 records from Reporte de avistamientos de oso palmero (Myrmecophaga tridactyla Linnaeus, 1758) en el área de influencia de Llanos 58, Puerto López, Meta, Colombia. 183 records from Oribatid mite communities (Acari: Oribatida) in different habitats of the Polistovsky Nature Reserve (Pskov Region, Russia). 8 records from Notes on Onciderini (Coleoptera, Cerambycidae, Lamiinae): description of a new species of Lesbates Dillon & Dillon and new distribution records. 7 records from A new species of pitviper of the genus Bothrops (Serpentes: Viperidae: Crotalinae) from the Central Andes of South America. 86 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 196 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 37 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 3836 records from Collection Herpetology SMF. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 1701 records from Waarneming.nl (NL) - Great Grey Shrike Count 2012-2013. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 16 records from Macroinvertebrate groups found on deep-sea volcanic habitats in the Galapagos Marine Reserve in the Eastern Tropical Pacific Ocean: Annelida. 4 records from Données naturalistes de PICHARD Olivier. 1 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 178 records from Corn bunting surveys on the Western Isles. 375 records from CG04_2017_12_18. 6 records from Two new taxa of Plebejus Kluk, 1780 (Lepidoptera, Lycaenidae) from the Gobi desert, Mongolia. 723 records from Données du/de la naturaliste CUENIN Sibylle provenant de la base de donnée du SINP Île-de-France CETTIA. 345 records from Kimberley Islands Biodiversity Survey (Bats). 3 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 6145 records from Plot-based observations of macrofungi in raised bogs in Western Siberia. 22 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 502 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 20 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 6240 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 1418 records from Invasive Non-Native Species. 17 records from Additions and corrections to the systematics of mayfly species assigned to the genus Callibaetis Eaton 1881 (Ephemeroptera: Baetidae) from South America. 3 records from A new Mediterranean species of Dolistenus (Diplopoda, Platydesmida, Andrognathidae), with an updated key for the genus and the first contribution for a barcode database of European Platydesmida. 93 records from Avon Baselining - Waterbirds. 3 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 84112 records from Denver Museum of Nature & Science - Entomology. 228 records from FBIP: Identification of polychaetes used as bait. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 8447 records from estuary metagenome Raw sequence reads. 9719 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16350 records from Database for alien invasive plants occurrences in Germany. 3 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 2 records from Hedotettix angulatus sp. nov. (Orthoptera: Tetrigoidea: Tetrigidae, Tetriginae) a new pygmy grasshopper species from India. 2 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 32 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 452 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 871 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 8313 records from 成龍溼地鳥類生態紀錄. 9 records from Herbier de Strasbourg. 98 records from RISC Non-Native Species Records for Rhododendron Leafhopper. 414 records from Naturschutzstation Schmidsfelden. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 80 records from BB-Biodiversität b. 3270 records from OUPR - Herbário "Professor José Badini". 237 records from Données du/de la naturaliste Jeliazkov Aliénor provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from Current knowledge on Mexican tardigrades with a description of Milnesium cassandrae sp. nov. (Eutardigrada: Milnesiidae) and discussion on the taxonomic value of dorsal pseudoplates in the genus Milnesium Doyère, 1840. 14295 records from National Biodiversity Data Bank. Observation records, 1900-2014. 16 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 109 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 19 records from The genus Anaphothrips (Thysanoptera, Thripidae) in China, with three new species. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 6045 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 39380 records from Vascular plant diversity in forests. 200795 records from Coral. 7277 records from Caddisfly (Trichoptera) records from Britain and Ireland, via iRecord. 426 records from Données du Centre de la mer de Biarritz. 1 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 5 records from A new species of Aethiopella Handschin, 1942 (Collembola, Poduromorpha, Neanuridae) from Neotropical Region, with comments on the genus. 5651 records from KUBI Mammalogy Collection. 92 records from Nottekanal, Klasse 7 - 10. 11 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 2733 records from RNF - Données du Parc Naturel Régional de la Forêt d'Orient. 245 records from données aranéologiques de CORNIC Jean-François. 86 records from Suivi de la flore patrimoniale de la RNR de Saint-Assise (77) dans le cadre d'un stage de M2. 74 records from Données espèces - Expertise IPE 69. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 107 records from 1st Austrian Birdrace (Wien). 115 records from Resilience of Antarctic marine benthic invertebrates and the ecological consequences of environmental change - Amphipod Data 2002/10. 54 records from Anfibios y reptiles de la serranía las Quinchas, Boyacá - Proyecto Boyacá BIO. 1 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 54393 records from Application INPN Espèces: Observations naturalistes, participatives et opportunistes, fondée sur des photographies. 2 records from New troglomorphic species of Tomocerus with well-developed postantennal organs (Collembola: Tomoceridae). 13 records from Coleção de Nematoda do Museu Nacional - UFRJ. 198 records from Impact of offshore oil drilling operations on the diversity of marine benthic Foraminifera - Raw sequence reads. 19770 records from Hoverflies (Syrphidae) of Ireland. 389 records from Données espèces - Expertise IQE 89. 26 records from Caracterización de la avifauna presente en el río Tutunendo, Municipio de Quibdó-Chocó. 5829 records from Inventory of plant species through Benin (West Africa). 4387 records from Colección de Plantas Vasculares del Herbario Forestal UDBC "Gilberto Emilio Mahecha Vega". 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 55 records from Revision of Australian species of the dung beetle genus Lepanus (Coleoptera: Scarabaeidae: Scarabaeinae): description of 10 new species from the L. australis, L. monteithi, and L. villosus species groups. 13 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 64 records from Livingstone Museum Bat Collection. 919 records from International Fossil Shell Museum (NL) - Mollusca Collection. 490 records from Données du/de la naturaliste Hasrouni Sami provenant de la base de donnée du SINP Île-de-France CETTIA. 3 records from First records of Composetia, Eunereis and Nectoneanthes (Annelida: Nereididae) from Taiwan, with descriptions of two new species. 4 records from A review of the deepwater cardinalfish genus Epigonus (Perciformes: Epigonidae) of the Western Indian Ocean, with description of two new species. 1 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 8606 records from Database of Marine Larval Fish Assemblages in Australian temperate and subtropical waters 1983 - 2016. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 200 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 511 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 20095 records from Microbial community in PAH-contaminated riverine sediments. 4 records from Reconsideration of the genera Merogomphus Martin, 1904, and Anisogomphus Selys, 1857, including erection of a new genus, with a new species and discussion of additional specimens from Cambodia. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 12 records from Rådgivende Biologer. 6 records from Moribaetis brachiostrinus (Ephemeroptera: Baetidae), a new species of mayfly from Costa Rica. 5 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 10 records from Three new species of Parapercis (Perciformes: Pinguipedidae) and first records of P. muronis (Tanaka, 1918) and P. rubromaculata Ho, Chang & Shao, 2012 from Australia. 564 records from Atewa Range Forest Reserve Bryophytes dataset, Ghana. 622 records from Feriendorf des Kreises Groß-Gerau/Ober-Seemen. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 1633 records from Regroupement de données Odonates du Département des Landes jusqu'en 2015. 7 records from Benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2010. 97 records from POPA- Fisheries Observer Program of the Azores: Sea turtle sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 36 records from BIOMEO_2017_12_18. 241 records from Bird Banding Data for Cockscomb Basin Wildlife Sanctuary, Belize 2016 - 2017. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 1827 records from Inventaire de la flore de la Communauté Urbaine de Bordeaux 2009. 615 records from Effect of climate-change induced glacier melting on the benthic prokaryotic diversity in the West Antarctic Peninsula. 76 records from Inventaire hivernal des nids de frelon asiatique. 2 records from Two new species of Bucculatrix Zeller (Lepidoptera: Bucculatricidae) from China. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 806 records from Phytoplankton abundance measured on water samples from rivers of the Lena Delta in 2009. 27 records from Bosque Mesófilo de Montaña de México. 51 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 5 records from Taxonomic revision of Stagmatoptera Burmeister, 1838 (Mantodea: Mantidae, Stagmatopterinae). 4290 records from EDP Foz-Tua: Terrestrial Birds (occasional observations)- Complementary Studies [2009-10]. 2348 records from Bell Museum fungi. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 22851 records from Données de Lépidoptères de Denis Vandromme. 102 records from BIRDRACE Westfälische Nachtigallen. 40719 records from Herbicide-incubated GBR lagoon microbiomes Targeted loci environmental. 11882 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 72 records from Phytoplankton abundance at station Rigel_2_2005-04 in April 2005, Chipana, Chile. 11 records from Redescription of the Indo-West Pacific cardinalfishes (Perciformes: Apogonidae) Rhabdamia spilota Allen & Kuiter 1994 and R. gracilis (Bleeker 1856). 10 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 231 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 12 records from Urban Barcode Project - Fungi. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 270 records from ACT and Southern Tablelands Weed Spotter. 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 46 records from Aktion Wiese und Wegrain Gitzenheide. 6 records from Two new species of bent toed geckos, Cyrtodactylus Gray, 1827 (Squamata: Gekkonidae) from Northeast India with comments on name-bearing types from the region. 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 41 records from Örtzemündung (Stedden). 708 records from Occurrences des observations de la campagne REMMOA Guyane (2008). 165 records from Données naturalistes de Monsieur VILAIN Frederic. 34521 records from National Stag Beetle Surveys (Great Stag Hunts). 1190 records from Tracking data from a free-roaming female cheetah released into the Pilanesberg National Park, South Africa. 3032 records from Fishes in MZNA-VERT: interactions between signal crayfish and fish communities. PhD project, Iván Vedia. 318 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 306-U1313. 2418127 records from Eremaea. 69424 records from Marine Offshore Seabed Survey data held by JNCC. 3 records from Morphological and molecular evidence for a new species of the genus Panolis Hübner, [1821] (Lepidoptera: Noctuidae). 316 records from Données naturalistes de Monsieur LEFEBVRE François. 12 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 1230 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 469 records from Natural History Museum Rotterdam (NL) - Chordata collection. 12 records from Mamíferos del municipio de Santa Bárbara, Santander - Proyecto Santander BIO. 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 1 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 106 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 23 records from Ackerrain Plönhagen. 2 records from New Notophthiracarus species (Acarina, Oribatida, Phthiracaridae) and overview of the distribution of the genus in South Africa. 11 records from Malawi-Histeridae-Biodiversity-Data. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 2036 records from Caracterización biológica de la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 10 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 8 records from New species of Andiorrhinus Cognetti, 1908 (Oligochaeta: Rhinodrilidae) from Venezuela and Brazil. 1 records from New enchytraeid species from Mount Hallasan (Jeju Island, Korea) (Enchytraeidae, Oligochaeta). 1 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 313 records from BIRDRACE Gätkes Erben. 4 records from A new species of Paratus Simon, 1898 (Araneae: Liocranidae, Paratinae) from India. 12 records from Revision of the genus Theopea Baly (Coleoptera: Chrysomelidae: Galerucinae) in Sundaland and the Philippines: Redefinition of the genus. 21 records from MEXU/Tipos de plantas vasculares. 23 records from Tümpel Schulbiologiezentrum. 491 records from Naturschutzgebiet Lüneburger Heide. 3 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1 records from Description of a new long-tailed skink (Scincidae: Trachylepis) from Angola and the Democratic Republic of the Congo. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 10 records from Bachpatenschaft Beeke. 22 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (4), 2011 - Données faune. 617 records from Listado taxonómico de la ictiofauna de la costa de Michoacán. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 3 records from A new species of Alonella Sars, 1862 (Crustacea: Cladocera: Chydoridae) from the Ecuadorian Andes. 11 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 14 records from Checklist of Cerambycidae (Coleoptera) primary types of the Coleção Entomológica Pe. Jesus Santiago Moure, Departamento de Zoologia, Universidade Federal do Paraná, Curitiba, Paraná, Brazil, Instituto Nacional de Pesquisas da Amazônia, Amazonas, Manaus, Brazil, and of the Museu Paraense. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 299 records from UAZ Mammals. 647 records from Données naturalistes de Daniel PAVON. 6 records from Cirripedia distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 40 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 25 records from Données Réseau National d’Échouages de Saint-Pierre et Miquelon. 2 records from Order Diptera, family Mydidae. 129 records from Malawi-Saturniidae-Biodiversity-Data. 60 records from Caracterización de la fauna reptiliana asociada a la cuenca del río Atrato, para el estudio de su navegabilidad, Quibdó - Chocó, 2012. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 258029 records from Estonian Nature Observations Database. 1 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 81 records from Bird specimens of Obihiro Centennial City Museum. 13754891 records from Southern African Bird Atlas Project 2. 1034 records from Botanical Museum, Copenhagen, Mycology Herbarium. 98 records from Etude d'impact de la ZAC Bellevue - compléments. 23853 records from Seasearch Marine Surveys in the Channel Islands. 9880 records from Fish Specimens. 13149 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 10066 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. 116 records from A revision of the genus Drasteria of Central Asia and Kazakhstan with special attention to the adjacent areas (Lepidoptera: Erebidae). 9936 records from NE Scotland fungus and lichen records 1800-2010. 1483 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 2 records from Description of the male of Antodice quadrimaculata Martins & Galileo, 2003 (Coleoptera, Cerambycidae, Lamiinae), with new country record for the species. 2724 records from LSUMZ Mammals Collection. 154 records from Données de la structure Philofauna provenant de la base de donnée du SINP Île-de-France CETTIA. 10 records from Five new species and new records of the spider genus Stemmops (Araneae, Theridiidae, Spintharinae) from Brazil. 40 records from Öhmdwiesen und Göldern (Konstanz). 450 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 462 records from Données du/de la naturaliste Borges Alexis provenant de la base de donnée du SINP Île-de-France CETTIA. 4875 records from Enquête nationale participative sur l'écureuil roux. 574 records from Survey data of rocky shores on the Monitoring sites 1000 project, BDCJ. 9348 records from Cumbria Non Native Invasive Species. 24 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 48 records from Suivi de la faune écrasée de la Réserve Naturelle Nationale des marais de Bruges. 487305 records from Finnish Winter Bird Census. 1 records from Morphological and molecular analyses confirm the occurrence of two sympatric Lysmata shrimp (Crustacea, Decapoda) in the southwestern Atlantic. 1 records from Squalius namak, a new chub from Lake Namak basin in Iran (Teleostei: Cyprinidae). 319 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cairngorms SSSI. 10 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 71 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 176 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 182 records from Monitoreo biológico en la cuenca Dagua - Subcuenca La Guinea ARA - RARE - CVC – Asociación Calidris. 494 records from Studies on archaeal communities from freshwater sediments based on 16S rRNA gene biomarker. 67968 records from England Non Native Species records 1965 to 2017. 12857 records from marine metagenome Raw sequence reads. 5472 records from Reptile Specimens. 1620 records from Colección del Herbario PSO de la Universidad de Nariño. 11 records from Chronicle of Nature - Phenology of Insects of FGBU GPZ Kologrivskij Les name after M.G. Sinicin. 33104 records from Natagriwal ; Observations made from operations within Natura 2000 habitats and other semi-natural areas. 9852 records from USBombus, contemporary survey data of North American bumble bees (Hymenoptera, Apidae, Bombus) distributed in the United States. 1 records from The nymph, habitat, and status of Eatonigenia in China (Ephemeroptera: Ephemeridae). 222 records from L’évaluation environnementale du projet du barrage de la retenue d'eau, de Guinea Alumina corporation à sangaredi, Boké (CESP2016-022). 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 2 records from New records of Iranian bark beetles (Coleoptera: Curculionidae, Scolytinae) and their host plants. 3350 records from Reef Check in Taiwan 台灣珊瑚礁體檢. 25 records from Thirteen new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China. 3 records from A new species of the genus Microgecko Nikolsky, 1907 (Sauria: Gekkonidae) from the southern Zagros Mountains, Iran. 800 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 1 records from Review of the Odontesthes perugiae species group from Río de La Plata drainage, with the description of a new species (Atherinomorpha: Atherinopsidae). 593 records from Océanopolis mammifères marins en Bretagne 1993-2015. 410 records from Caracterización ecológica de la vegetación asociada al humedal costero el Cuerval del municipio de Timbiquí- Cauca. 8 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 246 records from Stoats in Orkney Facebook page records & sightings, 2014 - 2015. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 787 records from Red list project inventory, vascular plants. 3027 records from Caracterización de fauna y flora para el establecimiento de límites funcionales de humedales en tres ventanas piloto: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo de humedales Paz de Ariporo - Hato Corozal. 7 records from New species and new records of Monohelea Kieffer from eastern Amazon, Brazil (Diptera: Ceratopogonidae). 1558 records from Nematode abundance in sediments obtained during RRS Charles Darwin cruise CD179. 240 records from Amphibians and Reptiles in Protected Areas in Ilocos Norte Province, Luzon Island, Northern Philippines. 4 records from Three new species of Daveyoungana Blocker & Webb (Hemiptera: Cicadellidae: Iassinae: Hyalojassini) from Brazil. 10 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 2 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 37 records from uncultured bacterium Targeted Locus (Loci). 110 records from BIRDRACE Linumer Luchschleicher. 2420 records from Hymenoptera collection, Natural History Museum, University of Oslo. 1 records from A new species of rock-dwelling gecko (Gekkonidae: Gehyra) from the Mt Surprise region of northern Queensland, Australia. 280 records from Lianas of the Guianas (Part Suriname). 2 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 7 records from Données naturalistes d'Olivier VILLEPOUX. 13 records from Diversidad de equinodermos en los cayos del norte, Reserva de Biósfera SeaFlower, 2011. 2135 records from NCSM Non-molluscan Invertebrates Collection. 237 records from Données du/de la naturaliste PLANCKE Michel provenant de la base de donnée du SINP Île-de-France CETTIA. 33 records from Données d'observation opportunistes collectées par la Réserve Naturelle Nationale de l'Ile du Grand-Connétable et le Groupe d'Etude et de Protection des Oiseaux en Guyane. 1908 records from The AAU Herbarium Database. 2 records from Lepidoptera and Coleoptera of the Forest Insect Museum Ibadan (FIMI) Nigeria. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 4 records from Two new species of the spider genus Belisana Thorell (Araneae: Pholcidae) from Xishuangbanna, Yunnan, China. 262 records from Herbier Ecole de Faune. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 1 records from A new Mapinguari Papavero & Wilcox (Diptera, Mydidae, Mydinae) from Minas Gerais State, Brazil. 1 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 4013 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 393 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 192 records from Colecção Entomológica do Museu de História Natural de Maputo. 2861 records from DMNS Marine Invertebrate Collection (Arctos). 1 records from New and rarely found species of asynaptine Porricondylinae (Diptera: Cecidomyiidae) in northern Europe. 722 records from Heritage Trees of Ireland. 6 records from An annotated checklist of the Iranian Dasytidae and Rhadalidae (Coleoptera: Cleroidea). 9 records from Données naturalistes de Laurent CORNILLE. 141 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 11 records from New species and new distributional records of Neotropical Mantispidae (Insecta: Neuroptera). 49 records from Natural Resources Wales North Wales Bat Roosts. 7699 records from Données oiseaux 2016 du Parc Naturel Régional du Perche. 5513 records from Heteroptera: Records for Kent. 60 records from Collection Polychaeta - ZSRO. 140 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 15680 records from imr_mareano_rpsledge. 1 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 8 records from RISC Non-Native Species Records for Zebra Mussel. 155 records from Birdrace-Gätkes_Erben-Lüneburg. 279 records from Liberian Greenbul Expedition 2013. 86 records from Oxic sediment - Microbial Metagenome. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 333 records from Macroarthropods, Isua 2013, Greenland. 41 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 147 (N.S) n° 40 (2), 2012 - Données faune. 7000 records from Inventario y base de datos de los líquenes de la selva seca de Jalisco. 153 records from Bird observations of UC Santa Barbara North Campus Open Space. 6 records from Acusana DeLong (Hemiptera: Cicadellidae: Gyponini), a genus not previously recorded in Brazil: description of four new species for the Brazilian fauna. 2869 records from Flora de los Parques Ecológicos Distritales Humedales de Bogotá D.C.. 1418 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 12 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 4 records from Vinogradovopleustes punctatum, new genus, new species, a pleustid amphipod from the Okhotsk Sea (Crustacea: Amphipoda: Gammaridea: Pleustidae: Pleusymtinae). 1 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 41 records from Wiese und Bach beim Unterbecken (Markersbach). 50 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 8 records from Schistura colossa and S. klydonion, two new species of loaches from Bolaven Plateau, southern Laos (Teleostei: Nemacheilidae). 59 records from UWIZM Phasmatodea. 19 records from Goethe-Hauptschule/Projekt I-10. 2 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 4168 records from Commissioned surveys and staff surveys and reports for Scottish Wildlife Trust reserves - Unassessed data. 2750 records from Gunma Museum of Natural History, Fungi Specimen. 1546 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 2 records from Kirchenforst. 7 records from Revision of the Australian bee fly genus Sisyromyia White, 1916 (Bombyliidae, Bombyliinae, Acrophthalmydini). 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 582 records from Bioblitz 2013 Copenhagen Denmark. 7 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 1988 records from PRECIS (KwaZulu-Natal Herbarium). 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 37 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 17 records from Kohlbach (Sulzfeld). 165 records from RV Investigator Voyage IN2016_V06 Seabird Observations, Australia (2016). 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from DD_cyano Targeted loci environmental. 3084 records from Spatial and environmental variation in whole microbial communities in Fildes Bay, King George Island, Antarctica Raw sequence reads. 66 records from Terrestrial isopods of the genus Porcellio Latreille, 1804 (Isopoda; Oniscidea) in Iran, with a description of a new species. 78 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Sorontorè) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 15724 records from Northern Gulf of Mexico Hypoxic Zone Raw sequence reads. 2 records from A new genus of calcareous sponge discovered in the Caribbean Sea: Bidderia gen. nov. (Porifera, Calcarea, Calcinea). 2810 records from National Parks Association of NSW Great Koala Count. 1333 records from Diversity of algae in wetlands. 539 records from étude entomologique de la ZSC du Bois de Vaires. 2220 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 163 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 18 records from Clitellata - SMF. 3 records from Review of Afrotropical species of Goetheana Girault (Hymenoptera: Eulophidae), with description of a new species. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 7646 records from SPC CoFish Invertebrates Observations Palau 2007. 210 records from The large carrion beetles (Coleoptera: Silphidae) of Turkey: a review with a new species record. 2 records from A new species of Physiculus (Teleostei: Moridae) from the Cape Verde Islands (Eastern Central Atlantic). 38 records from Fish Fauna of Berlin. 10 records from Endemic flora of Nepal at KATH. 5 records from Five new species of the spider genus Pholcus Walckenaer, 1805 (Araneae: Pholcidae) from China and Thailand. 1287 records from The occurrence status (present/absent) of the fish species associated with the ECOREEF, Discovery Bay, Jamaica (2015-2017). 658 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 51 records from Birds occurring at Namitete farm, Mchinji. 2595 records from Nijmegen Natural History Museum (NL) - Herbarium. 329 records from AT26-10 Crab Spa IGT incubations raw sequence reads. 1 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 112 records from Gunma Museum of Natural History, Fish Specimen. 289 records from Chronicle of Nature - Phenology of Plants of Volzhsko-Kamsky National Nature Biosphere Rezerve. 7 records from Grundschule Sandheide. 2142 records from Herbarium WRSL, Lichens Collection. 1283402 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 125055 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 5271 records from Kenya Virtual Museum Records. 165 records from UCM Fish Collection (Arctos). 246 records from Área Puracé - Proporcion de area ocupada Danta Puracé, 2017. 3 records from Revision of the flightless click-beetle genus Neodima Schimmel & Platia (Elateridae: Dimini) endemic to China, with comments on its systematic position. 957 records from Département_du_Var_2017_12_18. 191 records from sediment microorganism Metagenome. 2850 records from Herbario Universidad de Caldas - FAUC. 127 records from Wildlife Observations Bardon Hill 31.5.09. 30 records from Review of the species of the Cirolana ‘ parva - group’ (Cirolanidae: Isopoda: Crustacea) in Indonesian and Singaporean waters. 14 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 28 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 2 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 13 records from Occasional sampling of Harpacticoida in Gulf of Kandalaksha (White Sea). 29 records from Chronicle of Nature - Phenology of Amphibia of Central Forest State Nature Biosphere Reserve. 1 records from Levensteiniella manusensis sp. nov., a new polychaete species (Annelida: Polynoidae) from deep-sea hydrothermal vents in the Manus Back-Arc Basin, Western Pacific. 3455 records from permafrost metagenome Targeted loci environmental. 10600 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 1 records from Tersilochinae (Hymenoptera: Ichneumonidae) from New Zealand. Part 2. Review of genera Kiwi gen. nov. and Zealochus Khalaim. 5605 records from Proyecto para compatibilizar el inventario de biota edáfica BGBD con el Sistema Nacional de Información sobre Biodiversidad. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 3139 records from CTD water column metabarcoding. 853 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 2 records from Mylabris (Mylabris) snizeki sp. nov. from Jordan, with a key to the Jordanian species of the nominotypical subgenus (Coleoptera: Meloidae). 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 202 records from Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 899 records from coastal sediments Targeted Locus (Loci). 21 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 6 records from New species of grasshopper genus Aptoceras Bruner, 1908 (Orthoptera, Acrididae, Ommatolampidinae, Ommtolampidiini) from Iguaçu National Park (Southern Brazil), including a taxonomic key and distribution data. 29 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 1392 records from Rasgos funcionales de plantas, anfibios y aves de estudios bióticos en el Complejo de Páramos Chingaza. 335 records from Données papillons en Auvergne, observations synthétisées par Philippe Bachelard 2001-2016, espèces déterminantes des ZNIEFF Massif Central.. 44758 records from Big Hedgehog Map records. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 1 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 338 records from Fort William Knotweed. 286 records from Données DORIS de la FFESSM. 437 records from Finnish Floristic Database (Literature Sources). 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 1 records from Cortinarius koldingensis - a new species of Cortinarius, subgenus Phlegmacium related to Cortinarius sulfurinus. 31930 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 632 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 24 records from Computarización de la Colección de plantas acuáticas mexicanas del Herbario Nacional (MEXU), 3a Etapa. 243 records from Inventaire avifaune 2014 du site N2000 Haute Cize : Pic d'Herrozate et forêt d'Orion – FR7212015. 12422923 records from iNaturalist Research-grade Observations. 1507 records from Medicinial plant species found in protected areas and riparian lands in Sudano-guinean and Sudanian agroecological zones. Data mobilized in the framework of BID National project BID-AF2015-0065-NAC and funded by EU. 1 records from New loricariid fishes from headwaters on Serra da Mantiqueira and Complexo do Espinhaço, Minas Gerais State, Brazil (Teleostei: Siluriformes: Loricariidae). 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 276 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 1 records from Two new species of rain beetle (Coleoptera: Pleocomidae: Pleocoma Le Conte, 1856) in the Pacific Northwest of the United State of America. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 124 records from Données du/de la naturaliste Legrand Eric provenant de la base de donnée du SINP Île-de-France CETTIA. 1292 records from University of Arizona Insect Collection. 103 records from BIRDRACE Die Otzberger. 1 records from Description of Penia mantillerii sp. nov. (Coleoptera: Elateridae: Dimini), with a key to Penia species from Vietnam and nearby areas. 2 records from A review species of the genus Ceroplastes (Hemiptera: Coccomorpha: Coccidae) in China. 6033 records from Données naturalistes de Vincent Prié. 33 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Nurgush. 747 records from Diagnostic écologique de la Forêt Régionale de Rougeau. 352 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 12568 records from Bacterial diversity in snow from mid-latitude mountain areas: Alps, Eastern Anatolia, Karakoram and Himalaya.. 102 records from BIRDRACE Willi goes Birding. 1785 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE293. 1 records from Immature stages of Laurotanyus travassosi Oliveira, Messias & Silva-Vasconce
Keywords: GBIF; biodiversity; species occurrences